Multilayer structures, packaging materials, and vacuum insulation materials
Patent Information
- Application Number
- JP2023053256
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-03-29
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-03-29
AI Technical Summary
【0010】 本発明によれば、EVOHを含み、溶融成形の際のネックイン及びダイビルドアップが抑制された樹脂組成物を用いて形成されたシーラント層(α)を有し、シーラント層(α)のガスバリア性の均一性が高く、且つヒートシール強度及びヒートシール後の外観が改善された多層構造体、並びにそれを用いた包装材及び真空断熱体を提供できる。
Smart Images

Figure 0007936764000001 
Figure 0007936764000002 
Figure 0007936764000003
Abstract
Description
Technical Field
[0001] The present invention relates to a multilayer structure, a packaging material, and a vacuum heat insulator.
Background Art
[0002] An ethylene-vinyl alcohol copolymer (hereinafter may be abbreviated as "EVOH" in some cases) is excellent in transparency, gas barrier properties, aroma retention, solvent resistance, oil resistance, heat sealability and the like, and by taking advantage of such properties, the ethylene-vinyl alcohol copolymer may be used as a heat-sealable film for food packaging materials, industrial chemical packaging materials, agrochemical packaging materials, pharmaceutical packaging materials, vacuum heat insulators and the like. Such a heat-sealable film is molded into packaging bags and other containers such as bottles. Melt molding is generally widely used for molding the film. Accordingly, the resin composition to be subjected to melt molding is required to have excellent long-run performance such that defects such as fish eyes and streaks do not occur even when melt molding is performed for a long time.
[0003] However, since EVOH has a relatively active hydroxyl group in its molecule, even inside an extruder in a state where oxygen is scarce, oxidation and crosslinking reactions proceed in a high-temperature molten state, which may produce thermally degraded products. In particular, when long-term continuous operation is performed, the thermally degraded products accumulate inside the molding machine and generate gels and agglomerates that cause fish eyes, and thus the EVOH resin composition may have insufficient long-run properties.
[0004] On the other hand, Patent Document 1 describes that a resin composition comprising EVOH and 0.01 to 100 ppm of an unsaturated aldehyde suppresses the occurrence of defects such as fish eyes, gels, and streaks, and is excellent in long-run properties.
Prior Art Documents
Patent Documents
[0005]
Patent Document 1
Summary of the Invention
[0006] When using the EVOH resin composition described in Patent Document 1, it was found that neck-in, where the width of the extruded film is smaller than the effective width of the die, can occur during film molding with a T-die. Furthermore, it was found that EVOH resin compositions prone to such neck-in tend to have uneven thickness in the width direction of the formed layer, and as a result, films obtained using this EVOH resin composition tend to have non-uniform gas barrier properties in different parts. After diligent research by the inventors, it was surprisingly discovered that an EVOH resin composition containing specific types of unsaturated aldehydes in specific ratios can suppress such neck-in. However, when attempting to suppress neck-in by adjusting the content of the multiple types of unsaturated aldehydes, it was found that depending on the ratio of the multiple types of unsaturated aldehydes, a new problem arises: die build-up (deposits on the outer surface of the die lip) tends to adhere to the outer surface of the discharge port (die lip) of the molten resin composition.
[0007] On the other hand, when the EVOH layer is used as a heat seal layer, the area in contact with the die lip is large, so die build-up can be a significant problem when the EVOH layer is co-extruded as the outermost layer of a multilayer structure, or when it is a single-layer film consisting only of the EVOH layer. Furthermore, it has been found that films obtained using EVOH resin compositions prone to such die build-up are more susceptible to the occurrence of streaks and other defects caused by die build-up, and these tend to reduce the heat seal strength.
[0008] The present invention has been made in light of these circumstances, and its objective is to provide a multilayer structure having a sealant layer (α) formed using a resin composition containing EVOH that suppresses neck-in and die build-up during melt molding, the sealant layer (α) having high uniformity of gas barrier properties, and improved heat seal strength and appearance after heat sealing, as well as a packaging material and a vacuum insulation body using the same. [Means for solving the problem]
[0009] The purpose of the above is, [1] A multilayer structure comprising a sealant layer (α) made of a resin composition and a base layer (β) containing a thermoplastic resin having a melting point of 190°C or higher, wherein the sealant layer (α) is the outermost layer, and the resin composition contains an ethylene-vinyl alcohol copolymer (A) (hereinafter sometimes abbreviated as "EVOH(A)") having an ethylene unit content of 20 mol% or more and 60 mol% or less, and crotonaldehyde (B1), and further contains at least one selected from the group consisting of 2,4-hexadienal (B2) and 2,4,6-octatrienal (B3), wherein the resin composition satisfies the following formulas (1) and (2); 2.0≦b1 / (b2+b3)<150.0 (1) b² + 2b³ ≤ 0.65 ···(2) In formulas (1) and (2) above, b1 is the content of crotonaldehyde (B1) relative to EVOH (A) (ppm), b2 is the content of 2,4-hexadienal (B2) relative to EVOH (A) (ppm), and b3 is the content of 2,4,6-octatrienal (B3) relative to EVOH (A) (ppm). [2] The multilayer structure of [1], wherein the total content of crotonaldehyde (B1), 2,4-hexadienal (B2), and 2,4,6-octatrienal (B3) relative to EVOH (A) (b1+b2+b3) is 0.01 ppm or more and 7.0 ppm or less in the resin composition; [3] A multilayer structure of [1] or [2] in which the resin composition has a crotonaldehyde (B1) content of 0.01 ppm or more and 4.0 ppm or less; [4] A multilayer structure of [1] to [3] in which the resin composition has a b2 content of 2,4-hexadienal (B2) of 0.005 ppm or more and 0.65 ppm or less; [5] The multilayer structure of [1] to [4] in which the resin composition has a b3 content of 2,4,6-octatrienal (B3) of 0.325 ppm or less; [6] A multilayer structure of [1] to [5] wherein the resin composition further comprises a conjugated polyene compound (C), and in the resin composition, the content c of the conjugated polyene compound (C) relative to EVOH (A) is 1 ppm or more and less than 300 ppm; [7] A multilayer structure of [6] in which the conjugated polyene compound (C) is sorbic acid; [8] A multilayer structure of [1] to [7] in which a sealant layer (α) and a substrate layer (β) are laminated via an adhesive layer (γ); [9] A multilayer structure of [1] to [8] having a multilayer film in which a sealant layer (α), an adhesive layer (γ), and a substrate layer (β) are directly laminated in this order;
[10] Multilayer structures of [1] to [9] in which EVOH(A) contains EVOH(Aa) and EVOH(Ab), the difference in melting points between EVOH(Aa) and EVOH(Ab) (Aa-Ab) is 8°C or more, and the mass ratio of EVOH(Aa) to EVOH(Ab) (Aa / Ab) is 60 / 40 or more and 95 / 5 or less;
[11] A multilayer structure of [1] to
[10] wherein at least a portion of EVOH(A) contains at least one structural unit selected from the group consisting of structural units represented by the following formula (I) and structural units represented by the following formula (II) in an amount of 0.3 mol% to 40 mol% relative to the total vinyl alcohol units of the at least portion of EVOH(A); [ka] [In the above formula (I), R 1 , R 2 and R 3 Each of these independently represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 10 carbon atoms, an alicyclic hydrocarbon group having 3 to 10 carbon atoms, an aromatic hydrocarbon group having 6 to 10 carbon atoms, or a hydroxyl group.1 , R 2 and R 3 may be bonded to each other in a pair (provided that the case where both of the pair among R 1 , R 2 and R 3 are hydrogen atoms is excluded). Part or all of the hydrogen atoms contained in the aliphatic hydrocarbon group having 1 to 10 carbon atoms, the alicyclic hydrocarbon group having 3 to 10 carbon atoms, and the aromatic hydrocarbon group having 6 to 10 carbon atoms may be substituted with a hydroxyl group, an alkoxy group, a carboxyl group or a halogen atom. In the above formula (II), R 4 , R 5 , R 6 and R 7 each independently represent a hydrogen atom, an aliphatic hydrocarbon group having 1 to 10 carbon atoms, an alicyclic hydrocarbon group having 3 to 10 carbon atoms, an aromatic hydrocarbon group having 6 to 10 carbon atoms, or a hydroxyl group. R 4 and R 5 , or R 6 and R 7 may be bonded to each other (provided that the case where both R 4 and R 5 , or R 6 and R 7 are hydrogen atoms is excluded). Part or all of the hydrogen atoms contained in the aliphatic hydrocarbon group having 1 to 10 carbon atoms, the alicyclic hydrocarbon group having 3 to 10 carbon atoms, and the aromatic hydrocarbon group having 6 to 10 carbon atoms may be substituted with a hydroxyl group, an alkoxy group, a carboxyl group or a halogen atom.]
[12] The multilayer structure according to any one of [1] to
[11] , further comprising a layer (δ) containing a thermoplastic resin having a melting point of less than 190°C;
[13] The multilayer structure according to any one of [1] to
[12] , wherein the heat seal strength measured in accordance with JIS Z1707 (2019) when the sealant layers (α) of the multilayer structure are pressure-bonded to each other for 1 second under the conditions of a temperature of 200°C and a pressure of 0.1 MPa using a hot plate type heat sealer is 20 N / 15 mm or more;
[14] A packaging bag comprising the multilayer structure according to any one of [1] to
[13] ;
[15] A vacuum heat insulator comprising the multilayer structure according to any one of [1] to
[14] ;
[16] The adsorption amount of synthetic pyrethroid in the sealant layer (α) is 10 ng / cm2 A multilayer structure of type [1] to
[15] that is less than [1];
[17] The amount of nicotine adsorbed by the sealant layer (α) is 1000 ng / cm³. 2 A multilayer structure of type [1] to
[16] that is less than [1]; This is achieved by providing [the necessary services / services]. [Effects of the Invention]
[0010] According to the present invention, it is possible to provide a multilayer structure having a sealant layer (α) formed using a resin composition containing EVOH that suppresses neck-in and die build-up during melt molding, the sealant layer (α) having high uniformity of gas barrier properties, and improved heat seal strength and appearance after heat sealing, as well as a packaging material and a vacuum insulation body using the same. [Modes for carrying out the invention]
[0011] In this specification, the term "surface (or surface layer)" in a multilayer structure does not refer to a distinction between front and back, but rather to an exposed surface. That is, a multilayer structure has two surfaces. Similarly, a multilayer structure has two outermost layers.
[0012] The multilayer structure of the present invention comprises a sealant layer (α) made of a predetermined resin composition and a base layer (β) containing a thermoplastic resin with a melting point of 190°C or higher. In addition to the layers described above, the multilayer structure may also include an adhesive layer (γ), a thermoplastic resin layer (δ), and other layers. Each layer will be described below.
[0013] [Sealant layer (α)] The sealant layer (α) is a layer made of a predetermined resin composition. The resin composition will be described in detail below.
[0014] (Resin composition) The resin composition comprises EVOH (A) and crotonaldehyde (B1), and further comprises at least one selected from the group consisting of 2,4-hexadienal (B2) and 2,4,6-octatrienal (B3), and satisfies the following formulas (1) and (2). 2.0≦b1 / (b2+b3)<150.0 (1) b² + 2b³ ≤ 0.65 ···(2) In formulas (1) and (2) above, b1 is the content of crotonaldehyde (B1) relative to EVOH (A) (ppm), b2 is the content of 2,4-hexadienal (B2) relative to EVOH (A) (ppm), and b3 is the content of 2,4,6-octatrienal (B3) relative to EVOH (A) (ppm). In this specification, the content expressed in ppm is the content on a mass basis.
[0015] A b1 / (b2+b3) value between 2.0 and less than 150.0 results in good neck-in resistance and reduced thickness variations in the resulting sealant layer (α). This increases the uniformity of the gas barrier properties of the sealant layer (α), and consequently, the uniformity of the gas barrier properties of the multilayer structure tends to improve. On the other hand, 2,4-hexadienal (B2) and 2,4,6-octatrienal (B3) affect die build-up, with 2,4,6-octatrienal (B3) having a particularly significant impact. Therefore, a b2+2b3 value of 0.65 ppm or less suppresses die build-up and increases the heat seal strength of the resulting multilayer structure. As a result, the multilayer structure can exhibit a good appearance even after heat sealing. Furthermore, this resin composition is less prone to producing blemishes, streaks, etc., even after repeated melt molding. Therefore, the multilayer structure obtained using this resin composition also has excellent recyclability. In this specification, crotonaldehyde (B1), 2,4-hexadienal (B2), and 2,4,6-octatrienal (B3) may be collectively referred to as unsaturated aliphatic aldehyde (B).
[0016] (EVOH(A)) EVOH(A) is a copolymer having ethylene units and vinyl alcohol units, with an ethylene unit content of 20 mol% to 60 mol%. EVOH(A) is usually obtained by saponification of an ethylene-vinyl ester copolymer. The production and saponification of ethylene-vinyl ester copolymers can be carried out by known methods. Examples of vinyl esters include vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl pivalate, vinyl versaticate, and other aliphatic carboxylic acid vinyl esters, with vinyl acetate being preferred.
[0017] The ethylene unit content of EVOH(A) is 20 mol% or more, preferably 25 mol% or more, and more preferably 27 mol% or more. The ethylene unit content of EVOH(A) is 60 mol% or less, preferably 55 mol% or less, and more preferably 50 mol% or less. If the ethylene unit content is less than 20 mol%, the thermal stability during melt extrusion decreases, gelation becomes more likely, and streaks, fish eyes, and other defects tend to occur. The occurrence of streaks, fish eyes, and other defects becomes particularly noticeable when operating at higher temperatures or speeds for longer periods than under general conditions. If the ethylene unit content exceeds 60 mol%, the gas barrier properties tend to decrease.
[0018] The degree of saponification of EVOH(A) is preferably 90 mol% or higher, more preferably 95 mol% or higher, and even more preferably 99 mol% or higher. When the degree of saponification of EVOH(A) is 90 mol% or higher, the resulting sealant layer (α) and multilayer structure tend to have good gas barrier properties, thermal stability, moisture resistance, etc. Furthermore, the degree of saponification may be 100 mol% or less, 99.97 mol% or less, or 99.94 mol% or less.
[0019] Furthermore, EVOH(A) may have other structural units other than ethylene units, vinyl alcohol units, and vinyl ester units, to the extent that the objectives of the present invention are not hindered. When EVOH(A) has the above-mentioned other structural units, the content of these other structural units relative to the total structural units of EVOH(A) is preferably 30 mol% or less, more preferably 20 mol% or less, even more preferably 10 mol% or less, even more preferably 5 mol% or less, and particularly preferably 1 mol% or less. Also, when EVOH(A) has the above-mentioned other structural units, their content may be 0.05 mol% or more, or 0.10 mol% or more. Other structural units mentioned above include, for example, unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, and itaconic acid, or their anhydrides, salts, or mono- or dialkyl esters; nitriles such as acrylonitrile and methacrylonitrile; amides such as acrylamide and methacrylamide; olefin sulfonic acids such as vinyl sulfonic acid, allyl sulfonic acid, and methallyl sulfonic acid, or their salts; vinylsilane compounds such as vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(β-methoxy-ethoxy)silane, and γ-methacryloxypropylmethoxysilane; and structural units derived from alkyl vinyl ethers, vinyl ketones, N-vinylpyrrolidone, vinyl chloride, vinylidene chloride, etc.
[0020] The above-mentioned other structural units may be at least one of the following: structural unit (I) represented by formula (I), structural unit (II) represented by formula (II), and structural unit (III) represented by formula (III).
[0021] [ka]
[0022] In equations (I), (II), and (III), R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , R9 , R 10 and R 11 Each of these independently represents a hydrogen atom, an aliphatic hydrocarbon group with 1 to 10 carbon atoms, an alicyclic hydrocarbon group with 3 to 10 carbon atoms, an aromatic hydrocarbon group with 6 to 10 carbon atoms, or a hydroxyl group. 1 , R 2 and R 3 One of the pairs, R 4 and R 5 , R 6 and R 7 They may be bonded together to form part of a ring structure. Some or all of the hydrogen atoms in the above C1-C10 aliphatic hydrocarbon group, C3-C10 alicyclic hydrocarbon group, and C6-C10 aromatic hydrocarbon group may be substituted with hydroxyl groups, alkoxy groups, carboxyl groups, or halogen atoms. In formula (III), R 12 and R 13 Each of these independently represents a hydrogen atom, a formyl group, or an alkanoyl group having 2 to 10 carbon atoms.
[0023] When EVOH(A) has the above structural units (I), (II), or (III), the flexibility and processing properties of the resin composition tend to improve, and the stretchability and thermoformability tend to be better.
[0024] In the above structural units (I), (II), or (III), examples of aliphatic hydrocarbon groups having 1 to 10 carbon atoms include alkyl groups and alkenyl groups, examples of alicyclic hydrocarbon groups having 3 to 10 carbon atoms include cycloalkyl groups and cycloalkenyl groups, and examples of aromatic hydrocarbon groups having 6 to 10 carbon atoms include phenyl groups.
[0025] In the above structural unit (I), the above R 1 , R 2 and R 3 Preferably, each of these is independently a hydrogen atom, a methyl group, an ethyl group, a hydroxyl group, a hydroxymethyl group, or a hydroxyethyl group. Among these, from the viewpoint of further improving the moldability of the resin composition, it is more preferable that each of these is independently a hydrogen atom, a methyl group, a hydroxyl group, or a hydroxymethyl group.
[0026] The method for incorporating the above structural unit (I) into EVOH(A) is not particularly limited, and examples include copolymerizing monomers induced to structural unit (I) in the polymerization of ethylene and vinyl ester. Monomers derived to structural unit (I) include alkenes such as propylene, butylene, pentene, and hexene; 3-hydroxy-1-propene, 3-acyloxy-1-propene, 3-acyloxy-1-butene, 4-acyloxy-1-butene, 3,4-diasiloxy-1-butene, 3-acyloxy-4-hydroxy-1-butene, 4-acyloxy-3-hydroxy-1-butene, 3-acyloxy-4-methyl-1-butene, 4-acyloxy-2-methyl-1-butene, 4-acyloxy-3-methyl-1-butene, 3,4-diasiloxy-2-methyl-1-butene, 4-hydroxy-1-pentene, 5-hydroxy-1-pentene, 4 Examples of alkenes having a hydroxyl group or ester group include 5-dihydroxy-1-pentene, 4-acyloxy-1-pentene, 5-acyloxy-1-pentene, 4,5-diasiloxy-1-pentene, 4-hydroxy-3-methyl-1-pentene, 5-hydroxy-3-methyl-1-pentene, 4,5-dihydroxy-3-methyl-1-pentene, 5,6-dihydroxy-1-hexene, 4-hydroxy-1-hexene, 5-hydroxy-1-hexene, 6-hydroxy-1-hexene, 4-acyloxy-1-hexene, 5-acyloxy-1-hexene, 6-acyloxy-1-hexene, and 5,6-diasiloxy-1-hexene. In particular, propylene, 3-acyloxy-1-propene, 3-acyloxy-1-butene, 4-acyloxy-1-butene, and 3,4-diasiloxy-1-butene are preferred from the viewpoint of copolymerization reactivity and the processability and gas barrier properties of the resulting sealant layer (α) and multilayer structure. "Asiloxy" is preferably acetoxy, specifically 3-acetoxy-1-propene, 3-acetoxy-1-butene, 4-acetoxy-1-butene, and 3,4-diacetoxy-1-butene. In the case of alkenes containing esters, they are converted to the above structural unit (I) during the saponification reaction.
[0027] In the above structural unit (II), R 4 and R 5 It is preferable that both are hydrogen atoms. In particular, R 4 and R 5 Both are hydrogen atoms, and the above R 6 and R 7 It is more preferable that one of them is an aliphatic hydrocarbon group having 1 to 10 carbon atoms and the other is a hydrogen atom. The aliphatic hydrocarbon group is preferably an alkyl group or an alkenyl group. From the viewpoint of particularly emphasizing the gas barrier properties in the resulting sealant layer (α) and multilayer structure, R 6 and R 7 It is more preferable that one of them is a methyl group or an ethyl group and the other is a hydrogen atom. Also, the above R 6 and R 7 One of them is (CH2) h It is even more preferable that the substituent is represented by OH (where h is an integer from 1 to 8), and the other atom is a hydrogen atom. (CH2) h In substituents represented by OH, h is preferably an integer from 1 to 4, more preferably 1 or 2, and even more preferably 1.
[0028] The method for incorporating the above structural unit (II) into EVOH(A) is not particularly limited. For example, a method of incorporating it by reacting EVOH(A) obtained by a saponification reaction with a monovalent epoxy compound can be used. As the monovalent epoxy compound, compounds represented by the following formulas (IV) to (X) are preferably used.
[0029] [ka]
[0030] In the above equations (IV) to (X), R 14 , R 15 , R 16 , R 17 and R 18Each of these independently represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 10 carbon atoms (alkyl groups, alkenyl groups, etc.), an alicyclic hydrocarbon group having 3 to 10 carbon atoms (cycloalkyl groups, cycloalkenyl groups, etc.), or an aliphatic hydrocarbon group having 6 to 10 carbon atoms (phenyl groups, etc.). Also, i, j, k, p, and q each independently represent an integer from 1 to 8. However, R 17 If R is a hydrogen atom, 18 It is a group other than a hydrogen atom.
[0031] Examples of monovalent epoxy compounds represented by formula (IV) above include epoxyethane (ethylene oxide), epoxypropane, 1,2-epoxybutane, 2,3-epoxybutane, 3-methyl-1,2-epoxybutane, 1,2-epoxypentane, 3-methyl-1,2-epoxypentane, 1,2-epoxyhexane, 2,3-epoxyhexane, 3,4-epoxyhexane, 3-methyl-1,2-epoxyhexane, 3-methyl-1,2-epoxyheptane, 4-methyl-1,2-epoxyheptane, 1,2-epoxyoctane, 2,3-epoxyoctane, 1,2-epoxynonane, 2,3-epoxynonane, 1,2-epoxydecane, 1,2-epoxydodecane, epoxyethylbenzene, 1-phenyl-1,2-epoxypropane, 3-phenyl-1,2-epoxypropane, etc. Examples of monovalent epoxy compounds represented by formula (V) above include various alkylglycidyl ethers, etc. Examples of monovalent epoxy compounds represented by formula (VI) include various alkylene glycol monoglycidyl ethers. Examples of monovalent epoxy compounds represented by formula (VII) include various alkenyl glycidyl ethers. Examples of monovalent epoxy compounds represented by formula (VIII) include various epoxy alkanols such as glycidol. Examples of monovalent epoxy compounds represented by formula (IX) include various epoxycycloalkanes. Examples of monovalent epoxy compounds represented by formula (X) include various epoxycycloalkenes.
[0032] Among the monovalent epoxy compounds mentioned above, epoxy compounds having 2 to 8 carbon atoms are preferred. Particularly from the viewpoint of ease of handling and reactivity of the compound, monovalent epoxy compounds having 2 to 6 carbon atoms are more preferred, and 2 to 4 carbon atoms are even more preferred. Furthermore, it is particularly preferred that the monovalent epoxy compound is a compound represented by formula (IV) or formula (V) above. Specifically, from the viewpoint of reactivity with EVOH(A), processability of the resin composition and the resulting sealant layer (α) and multilayer structure, and gas barrier properties, 1,2-epoxybutane, 2,3-epoxybutane, epoxypropane, epoxyethane, or glycidol are preferred, with epoxypropane or glycidol being more preferred among them.
[0033] In the above structural unit (III), R 8 , R 9 , R 10 and R 11 The aliphatic hydrocarbon group is preferably a hydrogen atom or an aliphatic hydrocarbon group having 1 to 5 carbon atoms, and such aliphatic hydrocarbon group is preferably a methyl group, ethyl group, n-propyl group, isopropyl group, n-butyl group, isobutyl group, tert-butyl group, or n-pentyl group.
[0034] The method for incorporating the above structural unit (III) into EVOH(A) is not particularly limited, and for example, the method described in Japanese Patent Application Publication No. 2014-034647 can be cited.
[0035] The lower limit of the melting point of EVOH(A) is preferably 140°C, more preferably 150°C, and even more preferably 160°C. On the other hand, the upper limit of the melting point is preferably 220°C, more preferably 210°C, and even more preferably 200°C. When the melting point of EVOH(A) is within the above range, melt moldability is improved, and neck-in and die build-up during melt molding tend to be further suppressed. The melting point of EVOH(A) can be the value measured by the method described in the examples.
[0036] EVOH(A) may be used alone or in combination of two or more types.
[0037] EVOH(A) may contain two types of EVOH(Aa) and EVOH(Ab) with different melting points. For example, when the melting point of the resin composition is measured by the method described in the examples, peak temperatures corresponding to each EVOH may be observed. Furthermore, the resin composition may have a phase-separated structure in which one EVOH is dispersed in the other, or it may be in a form in which the two types of EVOH are completely miscible. EVOH(Aa) and EVOH(Ab) may be two types of EVOH with different ethylene unit content.
[0038] When EVOH(A) contains two types of EVOH(Aa) and EVOH(Ab) with different melting points, the lower limit of the difference in melting points between EVOH(Aa) and EVOH(Ab) (Aa-Ab), i.e., the value obtained by subtracting the melting point of EVOH(Ab) from the melting point of EVOH(Aa), may be, for example, 5°C, but 8°C is preferred. When this melting point difference is 8°C or higher, moldability and other properties are improved. The lower limit of this melting point difference is more preferably 12°C, even more preferably 16°C, even more preferably 20°C, and even more preferably 24°C. The lower limit of this melting point difference may further be 30°C, 40°C, 50°C, or 60°C. The upper limit of the difference in melting points between EVOH(Aa) and EVOH(Ab) may be, for example, 100°C, but 90°C is preferred, and 80°C, 70°C, 60°C, 50°C, 40°C, or 30°C may be more preferred. By setting the above melting point difference to above the above lower limit, the moldability and heat stretchability of the resin composition can be improved. Conversely, by setting the above melting point difference to below the above upper limit, the gas barrier properties and the effect of suppressing flow marks during long-run (long-term continuous operation) of the resin composition can be improved.
[0039] The lower limit of the melting point of EVOH(Aa) is preferably 150°C, more preferably 160°C, and even more preferably 170°C. On the other hand, the upper limit of the melting point is preferably 220°C, more preferably 210°C, and even more preferably 200°C. When the melting point of EVOH(Aa) is within the above range, melt moldability is improved, and neck-in and die build-up during melt molding tend to be further suppressed.
[0040] The lower limit of the ethylene unit content of EVOH(Aa) is preferably 20 mol%, more preferably 23 mol%, and even more preferably 25 mol%. On the other hand, the upper limit of the ethylene unit content of EVOH(Aa) is preferably 50 mol%, more preferably 47 mol%, and even more preferably 43 mol%, 40 mol%, or 35 mol%. By setting the ethylene unit content of EVOH(Aa) to be above the lower limit, the moldability, flexibility, and other effects of the resin composition and the resulting sealant layer (α) are fully realized. On the other hand, by setting the ethylene unit content of EVOH(Aa) to be below the upper limit, the gas barrier properties of the resin composition and the sealant layer (α) and multilayer structure obtained from the resin composition can be improved.
[0041] The degree of saponification of EVOH(Aa) is preferably 90 mol% or higher, more preferably 95 mol% or higher, and even more preferably 99 mol% or higher. When the degree of saponification of EVOH(Aa) is 90 mol% or higher, the gas barrier properties, thermal stability, moisture resistance, etc., tend to be good in the resin composition, and in the sealant layer (α) and multilayer structure obtained from the resin composition. Furthermore, the degree of saponification of EVOH(Aa) may be 100 mol% or less, 99.97 mol% or less, or 99.94 mol% or less.
[0042] The lower limit of the melting point of EVOH(Ab) is preferably 90°C, more preferably 100°C, and even more preferably 110°C, 120°C, 130°C, 140°C, or 150°C. On the other hand, the upper limit of the melting point is preferably 220°C, more preferably 210°C, even more preferably 200°C, and even more preferably 190°C, 180°C, or 170°C. When the melting point of EVOH(Ab) is within the above range, melt moldability is improved, and neck-in and die build-up during melt molding tend to be further suppressed.
[0043] The lower limit of the ethylene unit content of EVOH(Ab) is preferably 30 mol%, more preferably 34 mol%, and even more preferably 38 mol%. On the other hand, the upper limit of the ethylene unit content of EVOH(Ab) is preferably 60 mol%, more preferably 55 mol%, and even more preferably 52 mol%. By setting the ethylene unit content of EVOH(Ab) to be above the lower limit, the moldability, flexibility, and other effects of the resin composition and the resulting sealant layer (α) can be fully achieved. On the other hand, by setting the ethylene unit content of EVOH(Ab) to be below the upper limit, the gas barrier properties of the resin composition and the resulting sealant layer (α) can be enhanced.
[0044] The preferred degree of saponification for EVOH(Ab) can be the same as that for EVOH(Aa).
[0045] The lower limit of the difference in ethylene unit content between EVOH(Ab) and EVOH(Aa) (Ab-Aa), that is, the value obtained by subtracting the ethylene unit content of EVOH(Aa) from the ethylene unit content of EVOH(Ab), is preferably 4.5 mol%, more preferably 8 mol%, even more preferably 12 mol%, and even more preferably 15 mol%. The upper limit of the above difference in ethylene unit content (Ab-Aa) is preferably 40 mol%, more preferably 30 mol%, and even more preferably 20 mol%. By setting the difference in ethylene unit content between EVOH(Ab) and EVOH(Aa) to be above the lower limit, the moldability, heat stretchability, etc., of the resin composition and the resulting sealant layer (α) can be improved. Conversely, by setting the above difference in ethylene unit content to be below the upper limit, the gas barrier properties of the resin composition can be further improved.
[0046] The lower limit of the mass ratio (Aa / Ab) of EVOH(Aa) to EVOH(Ab), that is, the mass ratio of the EVOH(Aa) content to the EVOH(Ab) content, is preferably 60 / 40, more preferably 62 / 38, and may be even more preferably 65 / 35, 68 / 32, 70 / 30, or 75 / 25. The upper limit of this mass ratio is preferably 95 / 5, more preferably 93 / 7, even more preferably 92 / 8, even more preferably 91 / 9, and may be even more preferably 85 / 15. When the mass ratio is within the above range, the moldability, flexibility, etc., of the resin composition and the resulting sealant layer (α) are excellent while maintaining gas barrier properties against various gases. For example, by setting the above mass ratio (Aa / Ab) to or above the lower limit, the gas barrier properties and oil resistance, etc., of the resin composition and the resulting sealant layer (α) can be improved. On the other hand, by keeping the above mass ratio (Aa / Ab) below the above upper limit, the moldability, flexibility, etc., of the resin composition and the resulting sealant layer (α) can be improved.
[0047] It is preferable that at least a portion of EVOH(A) has at least one structural unit (x) selected from the group consisting of the structural unit represented by formula (I) and the structural unit represented by formula (II) below, from the viewpoint of improving the moldability, flexibility, etc., of the resin composition and the resulting sealant layer (α). In particular, it is preferable that EVOH(Ab) has structural unit (x).
[0048] In EVOH having at least some structural units (x) which are EVOH(A), the lower limit of the content of structural unit (x) relative to the total vinyl alcohol structural units is preferably 0.3 mol%, more preferably 1 mol%, and even more preferably 3 mol%. By setting the content of structural unit (x) to above the above lower limit, the moldability, flexibility, etc., of the resin composition and the resulting sealant layer (α) can be sufficiently improved. On the other hand, the upper limit of this content is preferably 40 mol%, more preferably 30 mol%, and even more preferably 20 mol%. By setting the content of structural unit (x) to below the above upper limit, gas barrier properties, etc., can be improved.
[0049] The EVOH(A) content in the resin composition is preferably 70% by mass or more, more preferably 80% by mass or more, particularly preferably 90% by mass or more, and may also be 95% by mass or more, 99% by mass or more, or 99.9% by mass or more, from the viewpoint of gas barrier properties, etc. The resin constituting the resin composition may be substantially composed of EVOH(A) alone. On the other hand, the EVOH(A) content in the resin composition may be, for example, 99.9% by mass or less, or 99% by mass or less.
[0050] (Unsaturated aliphatic aldehyde (B)) The resin composition contains crotonaldehyde (B1) and further comprises at least one selected from the group consisting of 2,4-hexadienal (B2) and 2,4,6-octatrienal (B3).
[0051] The lower limit of the content b1 of crotonaldehyde (B1) relative to EVOH (A) in the resin composition is preferably 0.01 ppm, more preferably 0.20 ppm, even more preferably 0.40 ppm, and in some cases, 0.70 ppm or 1.20 ppm may be preferred. On the other hand, the upper limit of the content b1 is preferably 4.0 ppm, more preferably 3.5 ppm, even more preferably 2.7 ppm, and in some cases, 2.0 ppm or 1.5 ppm may be preferred. When the content b1 is within the above range, it becomes easier to adjust the values of b1 / (b2+b3), b1+b2+b3 and b2+2b3, which will be described later, to a suitable range. In addition, when the content b1 is within the above range, discoloration tends to be suppressed.
[0052] In one embodiment, the resin composition contains 2,4-hexadienal (B2) in a specific ratio to crotonaldehyde (B1), which tends to suppress dye buildup while exhibiting excellent neck-in resistance. The lower limit of the content b2 of 2,4-hexadienal (B2) relative to EVOH (A) in the resin composition is preferably 0.005 ppm, more preferably 0.01 ppm, and even more preferably 0.02 ppm. On the other hand, the upper limit of the content b2 is preferably 0.65 ppm, more preferably 0.20 ppm, even more preferably 0.10 ppm, even more preferably 0.08 ppm, and particularly preferably 0.06 ppm. When the content b2 is within the above range, it becomes easier to adjust the values of b1 / (b2+b3), b1+b2+b3, and b2+2b3, which will be described later, to a suitable range. In addition, when the content b2 is within the above range, discoloration tends to be suppressed.
[0053] In one embodiment, the resin composition contains 2,4,6-octatrienal (B3) in a specific ratio to crotonaldehyde (B1), which tends to suppress die buildup while exhibiting excellent neck-in resistance. Compared to 2,4-hexadienal (B2), 2,4-octatrienal (B3) has a greater impact on die buildup with respect to the amount added. Therefore, from the viewpoint of suppressing die buildup while improving neck-in resistance, it is preferable that the resin composition contains 2,4-hexadienal (B2) rather than 2,4,6-octatrienal (B3). The upper limit of the content b3 of 2,4,6-octatrienal (B3) relative to EVOH (A) in the resin composition is preferably 0.325 ppm, more preferably 0.23 ppm, even more preferably 0.07 ppm, and particularly preferably 0.04 ppm. The lower limit of the content B3 may be 0 ppm or 0.005 ppm. When the content b3 is within the above range, it becomes easier to adjust the values of b1 / (b2+b3), b1+b2+b3, and b2+2b3, which will be described later, to a suitable range. In addition, when the content b3 is within the above range, discoloration tends to be suppressed.
[0054] In this resin composition, the ratio of the total content of 2,4-hexadienal (B2) b2 (ppm) and 2,4,6-octatrienal (B3) b3 (ppm) to the content of crotonaldehyde (B1) b1 (ppm) (b1 / (b2+b3)) is 2.0 or more and less than 150.0, resulting in excellent neck-in resistance. This neck-in resistance is an effect not seen when any of the unsaturated aliphatic aldehyde (B) compounds are used alone, and is only achieved when b1 / (b2+b3) falls within a specific range. The lower limit of b1 / (b2+b3) is preferably 4.0, more preferably 8.0. On the other hand, the upper limit of b1 / (b2+b3) is preferably 60.0, more preferably 25.0, and even more preferably 13.0. By keeping b1 / (b2+b3) within the above range, neck-in can be suppressed more effectively. As a result, the uniformity of the thickness of the resulting sealant layer (α) is improved, thereby increasing the uniformity of the gas barrier properties and heat seal strength of the sealant layer (α) and the multilayer structure.
[0055] In the resin composition, the upper limit of the sum of the content of 2,4-hexadienal (B2) b2 (ppm) and twice the content of 2,4,6-octatrienal (B3) b3 (ppm) (b2+2b3) is 0.65 ppm or less, preferably 0.50 ppm, more preferably 0.30 ppm, and even more preferably 0.10 ppm. If b2+2b3 exceeds the above upper limit, the occurrence of die buildup cannot be suppressed. If die buildup occurs, the resulting sealant layer (α) will have streaks and the like due to the die buildup, which will cause a decrease in heat seal strength and gas barrier properties in the multilayer structure. b2+2b3 may be 0.005 ppm or more, or 0.01 ppm or more.
[0056] In the resin composition, the upper limit of the total content (b1+b2+b3) of crotonaldehyde (B1), 2,4-hexadienal (B2), and 2,4,6-octatrienal (B3) relative to EVOH (A) is preferably 7.0 ppm, more preferably 4.0 ppm, even more preferably 3.5 ppm, even more preferably 3.0 ppm, even more preferably 1.5 ppm, and in some cases particularly preferably 1.0 ppm. By keeping b1+b2+b3 below the above upper limit, the discoloration of the resin composition can be sufficiently suppressed. On the other hand, the lower limit of b1+b2+b3 is preferably 0.01 ppm, more preferably 0.10 ppm, and in some cases even more preferably 0.30 ppm or 0.50 ppm.
[0057] (Conjugated polyene compound (C)) The resin composition preferably further contains a conjugated polyene compound (C). The conjugated polyene compound (C) can suppress the deterioration of color tone due to oxidative degradation of EVOH (A) during melt molding. Here, a conjugated polyene compound (C) is a compound having a structure in which carbon-carbon double bonds and carbon-carbon single bonds are alternately linked, and the number of carbon-carbon double bonds is two or more, in other words, a compound having a conjugated double bond. However, 2,4-hexadienal (B2) and 2,4,6-octatrienal (B3) are not considered to be conjugated polyene compounds (C). The conjugated polyene compound (C) may be a conjugated diene having two conjugated double bonds, a conjugated triene having three conjugated double bonds, or a conjugated polyene having more than that number. Furthermore, there may be multiple sets of conjugated double bond structures in one molecule. For example, compounds with three conjugated triene structures in the same molecule, such as tung oil, are also included in the category of conjugated polyene compounds (C). A preferred upper limit for the number of conjugated double bonds in the conjugated polyene compound (C) is seven. If the resin composition contains a conjugated polyene compound (C) having eight or more conjugated double bonds, the likelihood of discoloration of the pellets and, consequently, the molded article increases.
[0058] In addition to the conjugated double bond, the conjugated polyene compound (C) may have other functional groups such as carboxyl groups and their salts, hydroxyl groups, ester groups, ether groups, amino groups, imino groups, amide groups, cyano groups, diazo groups, nitro groups, sulfone groups and their salts, sulfonyl groups, sulfoxide groups, sulfide groups, thiol groups, phosphate groups and their salts, phenyl groups, halogen atoms, double bonds, triple bonds, etc.
[0059] The lower limit of the number of carbon atoms in the conjugated polyene compound (C) is preferably 4. The upper limit of the number of carbon atoms in the conjugated polyene compound (C) is preferably 30, and more preferably 10.
[0060] Examples of conjugated polyene compounds (C) include isoprene, 2,3-dimethyl-1,3-butadiene, 2,3-diethyl-1,3-butadiene, 2-t-butyl-1,3-butadiene, 1,3-pentadiene, 2,3-dimethyl-1,3-pentadiene, 2,4-dimethyl-1,3-pentadiene, 3,4-dimethyl-1,3-pentadiene, and 3-ethyl-1,3-pentadie. 2-methyl-1,3-pentadiene, 3-methyl-1,3-pentadiene, 4-methyl-1,3-pentadiene, 1,3-hexadiene, 2,4-hexadiene, 2,5-dimethyl-2,4-hexadiene, 1,3-octadiene, 1,3-cyclopentadiene, 1,3-cyclohexadiene, 1-phenyl-1,3-butadiene, 1,4-diphenyl-1,3-butadiene Examples include conjugated diene compounds such as ene, 1-methoxy-1,3-butadiene, 2-methoxy-1,3-butadiene, 1-ethoxy-1,3-butadiene, 2-ethoxy-1,3-butadiene, 2-nitro-1,3-butadiene, chloroprene, 1-chloro-1,3-butadiene, 1-bromo-1,3-butadiene, 2-bromo-1,3-butadiene, ocimene, phellandrene, myrcene, farnesene, sorbic acid, sorbate esters, and sorbates; conjugated triene compounds such as 1,3,5-hexatriene, 2,4,6-octatriene-1-carboxylic acid, eleostearic acid, tung oil, cholecalciferol, flubene, and tropone; and cyclooctatetraene, 2,4,6,8-decatetraene-1-carboxylic acid, retinol, and retinoic acid.
[0061] The conjugated polyene compound (C) is preferably sorbic acid, sorbate ester, sorbate salt, myrcene, or a mixture of two or more of these, and more preferably sorbic acid, sorbate salt (sodium sorbate, potassium sorbate, etc.), or a mixture thereof. Sorbic acid, sorbate salt, or a mixture thereof is preferred from the viewpoint of hygiene and availability because it has a high effect in suppressing oxidative degradation at high temperatures and is also widely used industrially as a food additive.
[0062] The molecular weight of the conjugated polyene compound (C) is usually 1,000 or less, preferably 500 or less, and more preferably 300 or less. When the molecular weight of the conjugated polyene compound (C) is below the above upper limit, the dispersion state of the conjugated polyene compound (C) in the resin composition becomes good, and the appearance after melt molding tends to improve. The lower limit of the molecular weight of the conjugated polyene compound (C) is, for example, 54, but it may also be 60 or 80.
[0063] The lower limit of the content c of the conjugated polyene compound (C) relative to EVOH(A) in the resin composition is preferably 1 ppm, and more preferably 3 ppm. Furthermore, the content c of the conjugated polyene compound (C) relative to EVOH(A) in the resin composition is preferably less than 300 ppm, more preferably 100 ppm or less, even more preferably 70 ppm or less, even more preferably 30 ppm or less, and particularly preferably 20 ppm or less or 10 ppm or less. When the content c of the conjugated polyene compound (C) is within the above range, the deterioration of hue during melt molding tends to be further suppressed.
[0064] (Other optional components) The resin composition may contain, as other optional components besides EVOH(A), unsaturated aliphatic aldehydes (B), and conjugated polyene compounds (C), boron compounds, carboxylic acids, phosphorus compounds, metal ions, antioxidants, UV absorbers, plasticizers, antistatic agents, lubricants, colorants, fillers, heat stabilizers, other resins besides EVOH(A), metal salts of higher aliphatic carboxylic acids, etc. The resin composition may contain two or more of these components. If the resin composition contains other optional components, the upper limit of their total content is preferably 1% by mass, and may also be preferably 0.5% by mass.
[0065] Boron compounds suppress gelation during melt molding and also suppress torque fluctuations (viscosity changes during heating) in extrusion molding machines, etc. Examples of the above boron compounds include boric acids such as orthoboric acid, metaboric acid, and tetraboric acid; boric acid esters such as triethyl borate and trimethyl borate; alkali metal salts or alkaline earth metal salts of the above boric acids, borates such as borax; and boron hydrides. Among these, boric acids are preferred, and orthoboric acid (hereinafter also referred to as "boric acid") is more preferred. The lower limit of the content of the boron compound relative to EVOH(A) is preferably 100 ppm, and more preferably 500 ppm. Furthermore, the upper limit of the content of the boron compound relative to EVOH(A) is preferably 5,000 ppm, more preferably 3,000 ppm, and even more preferably 1,000 ppm. By setting the content of the boron compound to be above the above lower limit, torque fluctuations in extrusion molding machines, etc. can be sufficiently suppressed. On the other hand, by keeping the boron compound content below the above upper limit, gelation during melt molding becomes less likely, improving the appearance of the multilayer structure. Note that the boron compound content is expressed as the orthoboric acid equivalent of the boron compound.
[0066] Carboxylic acids prevent discoloration of the sealant layer (α) and suppress gelation during melt molding. Examples of carboxylic acids include formic acid, acetic acid, propionic acid, butyric acid, lactic acid, and their salts. Preferred carboxylic acids are those with 4 or fewer carbon atoms or saturated carboxylic acids, with acetic acid being more preferred. These acetic acids include acetic acid and acetate salts. It is preferable to use acetic acid and acetate salts in combination, and more preferable to use acetic acid and sodium acetate in combination. The lower limit of the carboxylic acid content relative to EVOH(A) is preferably 50 ppm, more preferably 100 ppm, and even more preferably 150 ppm. The upper limit of the carboxylic acid content relative to EVOH(A) is preferably 1,000 ppm, more preferably 500 ppm, and even more preferably 400 ppm. By setting the carboxylic acid content above the above lower limit, a sufficient discoloration suppression effect can be obtained, and the occurrence of yellowing can be sufficiently suppressed. On the other hand, by keeping the carboxylic acid content below the above upper limit, gelation is less likely to occur during melt molding, especially during long melt molding periods, resulting in a better appearance of the multilayer structure.
[0067] Phosphorus compounds suppress the occurrence of defects such as streaks and fish eyes, as well as discoloration, and improve long-run performance. Examples of phosphorus compounds include phosphates such as phosphoric acid and phosphorous acid. The phosphate may be in the form of monophosphate, diphosphate, or tertiary phosphate. The cation species of the phosphate is not particularly limited, but alkali metal salts and alkaline earth metal salts are preferred, of which sodium dihydrogen phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate, and dipotassium hydrogen phosphate are more preferred, and sodium dihydrogen phosphate and dipotassium hydrogen phosphate are even more preferred. The lower limit of the phosphorus compound content relative to EVOH(A) is preferably 1 ppm, more preferably 10 ppm, even more preferably 20 ppm, and particularly preferably 30 ppm. The upper limit of the phosphorus compound content relative to EVOH(A) is preferably 200 ppm, more preferably 150 ppm, and even more preferably 100 ppm. By setting the phosphorus compound content above the lower limit or below the upper limit, thermal stability is improved, and the formation of gel-like particles and discoloration during long-term melt molding becomes less likely.
[0068] Examples of metal ions include monovalent metal ions, divalent metal ions, and other transition metal ions, which may consist of one or more types. Among these, monovalent metal ions and divalent metal ions are preferred. Among monovalent metal ions, alkali metal ions are preferred, such as lithium, sodium, potassium, rubidium, and cesium ions, with sodium or potassium ions being preferred from the viewpoint of industrial availability. Examples of alkali metal salts that provide alkali metal ions include aliphatic carboxylates, aromatic carboxylates, carbonates, hydrochlorides, nitrates, sulfates, phosphates, and metal complexes. Among these, aliphatic carboxylates and phosphates are preferred from the viewpoint of availability, and specifically, sodium acetate, potassium acetate, sodium phosphate, and potassium phosphate are preferred. It is also preferable to include divalent metal ions as metal ions. When the metal ions include divalent metal ions, for example, the thermal degradation of EVOH when trim is recovered and reused may be suppressed, and the generation of gel and blemishes in the resulting molded article may be suppressed. Examples of divalent metal ions include beryllium, magnesium, calcium, strontium, barium, and zinc ions, but magnesium, calcium, or zinc ions are preferred from the viewpoint of industrial availability. Examples of divalent metal salts that provide divalent metal ions include carboxylates, carbonates, hydrochlorides, nitrates, sulfates, phosphates, and metal complexes, with carboxylates being preferred. Preferred carboxylic acids constituting the carboxylates are carboxylic acids having 1 to 30 carbon atoms, specifically including acetic acid, propionic acid, butyric acid, stearic acid, lauric acid, montanic acid, behenic acid, octic acid, sebacic acid, ricinoleic acid, myristic acid, palmitic acid, etc., with acetic acid and stearic acid being preferred among them. The lower limit of the metal ion content in EVOH(A) is preferably 1 ppm, more preferably 100 ppm, and even more preferably 150 ppm. On the other hand, the upper limit of the metal ion content is preferably 1,000 ppm, more preferably 400 ppm, and even more preferably 350 ppm. When the metal ion content relative to EVOH(A) is 1 ppm or higher, the resulting multilayer structure tends to exhibit good interlayer adhesion.On the other hand, when the metal ion content is 1,000 ppm or less, the stain resistance tends to be good.
[0069] Examples of antioxidants include 2,5-di-t-butylhydroquinone, 2,6-di-t-butyl-p-cresol, 4,4'-thiobis(6-t-butylphenol), 2,2'-methylene-bis(4-methyl-6-t-butylphenol), and octadecyl-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate. Examples of ultraviolet absorbers include ethylene-2-cyano-3,3'-diphenyl acrylate, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3'-t-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-hydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, and 2-hydroxy-4-oxybenzophenone.
[0070] Examples of plasticizers include dimethyl phthalate, diethyl phthalate, dioctyl phthalate, wax, liquid paraffin, and phosphate esters. Examples of antistatic agents include pentaerythritol monostearate, sorbitan monopalmitate, sulfated polyolefins, polyethylene oxide, and polyethylene glycol (trade name: Carbowax).
[0071] Examples of lubricants include ethylene bisstearamide and butyl stearate. Examples of colorants include carbon black, phthalocyanine, quinacridone, indoline, azo pigments, and red iron oxide. Examples of fillers include glass fiber, wollastonite, calcium silicate, talc, and montmorillonite. Examples of heat stabilizers include hindered phenol compounds and hindered amine compounds.
[0072] Other resins besides EVOH(A) include, for example, polyamides and polyolefins. Examples of metal salts of higher aliphatic carboxylic acids include, for example, sodium stearate, potassium stearate, calcium stearate, and magnesium stearate.
[0073] In the resin composition, the total content of EVOH (A) and unsaturated aliphatic aldehydes (B) (crotonaldehyde (B1), 2,4-hexadienal (B2), and 2,4,6-octatrienal (B3)) is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 98% by mass or more, and particularly preferably 99% by mass or more. The resin composition may consist substantially of EVOH (A) and unsaturated aliphatic aldehydes (B), or it may consist solely of EVOH (A) and unsaturated aliphatic aldehydes (B). In this specification, "substantially consisting of..." means that the inclusion of optional components is permitted as long as it does not affect the effects of the present invention, and in this specification, "consisting only of" means that optional components other than impurities that are inevitably included are excluded. The sealant layer (α) preferably consists solely of the resin composition.
[0074] The lower limit of the melt flow rate (MFR) of the resin composition at 210°C and a load of 2,160 g is preferably 0.5 g / 10 min, and more preferably 1 g / 10 min. On the other hand, the upper limit of the MFR is preferably 30 g / 10 min, and more preferably 20 g / 10 min. Having the MFR of the resin composition within the above range can improve melt moldability and other properties. Furthermore, having the MFR of the resin composition within the above range tends to result in better neck-in resistance.
[0075] <Method for preparing resin compositions> The method for producing the resin composition is not particularly limited as long as it allows for the blending of an unsaturated aliphatic aldehyde (B) into EVOH (A). For example, the production method could be: (1) A step of copolymerizing ethylene and vinyl ester, and (2) A step of saponifying the copolymer obtained in step (1). A method for producing a resin composition comprising the above, characterized in that the resin composition contains a predetermined amount and a predetermined ratio of unsaturated aliphatic aldehyde (B).
[0076] There are no particular limitations on the method for incorporating unsaturated aliphatic aldehyde (B) into the resin composition, but examples include adding unsaturated aliphatic aldehyde (B) in step (1) above, adding unsaturated aliphatic aldehyde (B) in step (2) above, or adding unsaturated aliphatic aldehyde (B) to EVOH (A) obtained in step (2) above. When adopting the method of adding unsaturated aliphatic aldehyde (B) in step (1) above, or the method of adding unsaturated aliphatic aldehyde (B) in step (2) above, it is necessary to increase the amount added in order to contain the desired amount of unsaturated aliphatic aldehyde (B) in the resulting resin composition, taking into account the amount consumed in the polymerization reaction in step (1) and the saponification reaction in step (2) above. Therefore, when adding unsaturated aliphatic aldehyde (B) in the polymerization reaction or saponification reaction step, it is preferable to add the amount of unsaturated aliphatic aldehyde (B) that will be consumed. On the other hand, the method of adding an unsaturated aliphatic aldehyde (B) to EVOH (A) obtained from step (2) above is superior in terms of operability because it can be added without considering consumption within the process.
[0077] Methods for adding unsaturated aliphatic aldehyde (B) to EVOH(A) include, for example, a method of pre-mixing unsaturated aliphatic aldehyde (B) with EVOH(A) and granulating pellets; a method of impregnating strands precipitated in a paste precipitation process after saponification of ethylene-vinyl ester copolymer with unsaturated aliphatic aldehyde (B); a method of impregnating strands after cutting with unsaturated aliphatic aldehyde (B); a method of adding unsaturated aliphatic aldehyde (B) to remelted chips of a dried resin composition; a method of melt-kneading a blend of each component of EVOH(A) and unsaturated aliphatic aldehyde (B); a method of feeding unsaturated aliphatic aldehyde (B) into the EVOH(A) molten material from the middle of the extruder to incorporate it; and a method of creating a masterbatch by granulating a portion of EVOH(A) with unsaturated aliphatic aldehyde (B) at a high concentration, and then dry-blending and melt-kneading it with EVOH(A).
[0078] Of these methods, a method of granulating pellets by pre-mixing unsaturated aliphatic aldehyde (B) with EVOH(A) is preferred, from the viewpoint of being able to uniformly disperse a trace amount of unsaturated aliphatic aldehyde (B) in EVOH(A). Specifically, a resin composition pellet in which unsaturated aliphatic aldehyde (B) is uniformly mixed with EVOH(A) can be obtained by adding unsaturated aliphatic aldehyde (B) to a solution obtained by dissolving EVOH(A) in a good solvent such as a water / methanol mixed solvent, extruding the mixed solution into a poor solvent through a nozzle or the like to precipitate and / or solidify it, and then washing and / or drying it.
[0079] Methods for incorporating components other than the unsaturated aliphatic aldehyde (B) into EVOH (A) include, for example, a method of melt-kneading the pellets together with the other components, a method of mixing the other components together with the unsaturated aliphatic aldehyde (B) when preparing the pellets, a method of immersing the pellets in a solution containing the other components, and a method of dry-blending the pellets with the other components. For mixing the other components, a ribbon blender, a high-speed mixer kneader, a mixing roll, an extruder, an intensive mixer, etc., can be used.
[0080] When used in the manufacture of the sealant layer (α), the resin composition is preferably in pellet form for ease of handling. The shape of the pellets of the resin composition is not particularly limited, but examples include cylindrical, prismatic, spherical, and lenticular. Among these, cylindrical, spherical, or lenticular pellets are preferred from the viewpoint of pellet transport stability, handling, and productivity. In the case of cylindrical pellets, the diameter is preferably 1 mm to 10 mm, more preferably 2 mm to 8 mm, and the height is preferably 1 mm to 10 mm, more preferably 2 mm to 8 mm, and even more preferably 3 mm to 5 mm. In the case of spherical or lenticular pellets, the length in the short direction is preferably 1 mm to 10 mm, more preferably 2 mm to 8 mm, and the length in the long direction is preferably 1 mm to 10 mm, more preferably 2 mm to 8 mm.
[0081] The average thickness of the sealant layer (α) is not particularly limited, and the lower limit may be, for example, 1 μm, 5 μm, 7 μm, or 10 μm. By setting the average thickness of the sealant layer (α) to be above the lower limit, gas barrier properties can be improved. On the other hand, the upper limit of the average thickness may be, for example, 100 μm, 70 μm, 50 μm, or 40 μm. Setting the average thickness of the sealant layer (α) to be below the upper limit tends to result in better appearance characteristics. Unless otherwise specified, the average thickness of the sealant layer (α) and each of the other layers is the average value of the thickness measured at five or more arbitrary locations.
[0082] In accordance with ISO 14663-2 annex C, the upper limit of oxygen permeability measured under conditions of 30°C and 65% RH for the sealant layer (α) is 50 mL / 20 μm / m². 2 • day • atm is preferred. 10 mL • 20 μm / m 2 • day • atm is more preferred 5 mL • 20 μm / m 2 •day·atm is even more preferred at 1 mL·20 μm / m² 2 Day ATM is particularly preferable.
[0083] (Single-layer film) The sealant layer (α) can be formed, for example, as a single-layer film (base film) made of the resin composition. The method of formation in this case is not particularly limited and includes, for example, melting, solution, and calendering, with the melting method being preferred. Examples of melting methods include casting and inflation, with the casting method being preferred.
[0084] In the case of film formation by the casting method, stretching may be performed. The stretching method is not particularly limited and may be uniaxial stretching, simultaneous biaxial stretching, or sequential biaxial stretching. The lower limit of the stretching ratio in terms of area is preferably 8 times, and more preferably 9 times. The upper limit of the stretching ratio is preferably 12 times, and more preferably 11 times. By keeping the stretching ratio within the above range, the uniformity of the film thickness, gas barrier properties, and mechanical strength can be improved.
[0085] When stretching, it is preferable to pre-moisten the raw material (film before stretching) with water. This facilitates continuous stretching. The lower limit of the moisture content of the raw material before stretching is preferably 2% by mass, more preferably 5% by mass, and even more preferably 10% by mass. The upper limit of the moisture content of the raw material before stretching is preferably 30% by mass, more preferably 25% by mass, and even more preferably 20% by mass.
[0086] The stretching temperature varies somewhat depending on the moisture content of the raw material before stretching and the stretching method, but is generally considered to be between 50°C and 130°C. In order to obtain a biaxially oriented film with minimal stretching unevenness, a stretching temperature of 70°C to 100°C is preferred for simultaneous biaxial stretching, 70°C to 100°C is preferred for longitudinal stretching on a roll in sequential biaxial stretching, and 80°C to 120°C is preferred for widthwise stretching on a tenter.
[0087] The sealant layer (α) may be one layer of a multilayer film (base film) that further has other layers. As a multilayer film, for example, a multilayer film (base film) can be made in which the sealant layer (α), the adhesive layer (γ) described later, and the thermoplastic resin layer (δ) described later are laminated in this order. Note that the multilayer film is not limited to the above layer structure, and may have a sealant layer (α) as one of the outermost layers and one or more other layers. However, it is preferable that the multilayer film has a thermoplastic resin layer (δ) together with the sealant layer (α), and it is even more preferable that it has an adhesive layer (γ) provided between the sealant layer (α) and the thermoplastic resin layer (δ).
[0088] The method for manufacturing multilayer films is not particularly limited and includes, for example, co-extrusion casting, co-extrusion inflation molding, and co-extrusion coating.
[0089] The overall thickness of the multilayer film can be set appropriately depending on the application. A total thickness of 10 μm or more is preferred, 13 μm or more is more preferred, and 15 μm or more is even more preferred. An overall thickness of 10 μm or more tends to improve industrial productivity. Furthermore, an overall thickness of 300 μm or less is preferred, 200 μm or less is more preferred, 100 μm or less is even more preferred, and 50 μm or less is particularly preferred. An overall thickness of 300 μm or less tends to improve industrial productivity.
[0090] It is preferable that the multilayer film is stretched. In this case, for example, if the multilayer film comprises at least a sealant layer (α), an adhesive layer (γ), and a thermoplastic resin layer (δ), it is preferable that the resulting vapor-deposited film is made up of at least the sealant layer (α), adhesive layer (γ), and thermoplastic resin layer (δ) stretched integrally. The degree of stretching is preferably 3 to 12 times in terms of area stretching ratio in at least one axial direction, more preferably 4 to 10 times, and even more preferably 5 to 8 times. A stretching ratio of 3 times or more improves gas barrier properties. On the other hand, a stretching ratio of 12 times or less results in a good film surface.
[0091] The multilayer film may be stretched in two axes as an area-based stretching ratio of 9 to 144 times, preferably 16 to 100 times, and more preferably 25 to 64 times. A stretching ratio of 9 times or more improves gas barrier properties. On the other hand, a stretching ratio of 144 times or less results in a good film surface.
[0092] The method for stretching a multilayer film is not particularly limited, and examples include tenter stretching, tubular stretching, and roll stretching. From the viewpoint of manufacturing cost, sequential biaxial stretching or simultaneous biaxial stretching by tenter stretching and tubular stretching is preferred. From the viewpoint of equipment cost, uniaxial stretching by roll stretching is preferred. Furthermore, if the multilayer film is an inflation-molded product, roll stretching is preferred from the viewpoint that the folded cylindrical multilayer film after inflation molding can be easily stretched in the uniaxial direction.
[0093] [Base material layer (β)] The base layer (β) is a layer containing a thermoplastic resin with a melting point of 190°C or higher, and by including the base layer (β), the appearance after heat sealing can be improved.
[0094] Examples of thermoplastic resins having a melting point of 190°C or higher include polyamide, polyester, polystyrene, polyvinyl chloride, poly(meth)acrylic acid ester, polyvinylidene chloride, polyacetal, polycarbonate, polyvinyl acetate, polyurethane, and polyacrylonitrile, with polyester being preferred and polyethylene terephthalate being more preferred.
[0095] The proportion of thermoplastic resin with a melting point of 190°C or higher in the base layer (β) is preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and may be 95% by mass or more, or 99% by mass or more, or substantially composed of thermoplastic resin with a melting point of 190°C or higher.
[0096] The average thickness of the substrate layer (β) is preferably 2 μm or more and 200 μm or less, more preferably 3 μm or more and 100 μm or less, and may also be 5 μm or more and 50 μm or less.
[0097] The base layer (β) may be one layer or two or more layers, and if there are two or more base layer layers (β), each base layer (β) may be the same or different.
[0098] [Adhesive layer (γ)] In the multilayer structure of the present invention, it is preferable that a sealant layer (α) and a substrate layer (β) are laminated via an adhesive layer (γ). More preferably, the adhesive layer (γ) is laminated directly onto the sealant layer (α). That is, it is more preferable that the sealant layer (α), adhesive layer (γ), and substrate layer (β) are laminated in this order without any other layers in between. Furthermore, if a thermoplastic resin layer (δ), which will be described later, is included, it is preferable to laminate it to the sealant layer (α) or the substrate layer (β) using the adhesive layer (γ).
[0099] The adhesive layer (γ) is not particularly limited as long as it is made of a material that enhances interlayer adhesion, but it is preferably an adhesive resin layer formed from an adhesive resin or an adhesive layer formed from an adhesive. As the adhesive resin, it is preferable to use a polyolefin having a carboxyl group, a carboxylic acid anhydride group, or an epoxy group. Since such an adhesive resin has excellent adhesion to the thermoplastic resin layer (δ) described later, when an adhesive resin layer is suitable as the adhesive layer (γ), the sealant layer (α) and the thermoplastic resin layer (δ) are laminated, and the layer configuration is sealant layer (α) / adhesive layer (γ) (adhesive resin layer) / thermoplastic resin layer (δ) when " / " means direct lamination.
[0100] Examples of polyolefins containing carboxyl groups include polyolefins copolymerized with acrylic acid or methacrylic acid. In this case, all or part of the carboxyl groups contained in the polyolefin may exist in the form of metal salts, as is typical of ionomers. Examples of polyolefins having carboxylic acid anhydride groups include polyolefins graft-modified with maleic anhydride or itaconic acid. Examples of polyolefins having epoxy groups include polyolefins copolymerized with glycidyl methacrylate. Among these, polyolefins having carboxylic acid anhydride groups such as maleic anhydride, and especially polyethylene and polypropylene having carboxylic acid anhydride groups, are preferred due to their excellent adhesive properties.
[0101] The melt flow rate (MFR) of the adhesive resin, measured at 190°C and a 2160g load according to JIS K 7210:2014, is preferably 0.1g / 10min to 20.0g / 10min, and more preferably 1.0g / 10min to 10.0g / 10min. When the MFR of the adhesive resin is within the above range, the film formation stability during molding tends to be good.
[0102] As the adhesive, a known adhesive can be used, and a two-component reactive polyurethane adhesive, which involves mixing and reacting a polyisocyanate component and a polyol component, is preferred. Furthermore, the adhesive properties can sometimes be further enhanced by adding a small amount of additive, such as a known silane coupling agent, to the adhesive layer. The adhesive is suitably used when manufacturing multilayer structures by lamination, and is suitably used when laminating a base layer (β) with other layers.
[0103] The average thickness of the adhesive layer (γ) is preferably 0.5 μm to 20 μm, and more preferably 1 μm to 10 μm, from the viewpoint of industrial productivity and quality stability. When the multilayer structure of the present invention has multiple sealant layers (α), a base layer (β), and a thermoplastic resin layer (δ), or when it includes an EVOH layer or the like different from the sealant layer (α), the adhesive layer (γ) may be provided between each layer, and the number of adhesive layers (γ) in the multilayer structure of the present invention is not particularly limited.
[0104] [Thermoplastic resin layer (δ)] The multilayer structure of the present invention can be made to have increased mechanical strength by including a thermoplastic resin layer (δ) containing a thermoplastic resin with a melting point of less than 190°C. Furthermore, by forming a film in multiple layers with a sealant layer (α), the film thickness of the sealant layer (α) tends to be reduced, and as a result, the recycling of the multilayer structure of the present invention tends to be easier. In addition, properties such as heat sealability and mechanical strength can be imparted depending on the type of thermoplastic resin that constitutes the thermoplastic resin layer (δ).
[0105] Thermoplastic resins with a melting point of less than 190°C include polyethylene such as linear low-density polyethylene, low-density polyethylene, ultra-low-density polyethylene, medium-density polyethylene, and high-density polyethylene; polyolefins such as ethylene-vinyl acetate copolymers, ionomers, ethylene-propylene (block or random) copolymers, ethylene-(meth)acrylic acid copolymers, ethylene-(meth)acrylic acid ester copolymers, polypropylene, propylene-α-olefin copolymers, polybutene, polypentene, and other olefins, either alone or in copolymer form, or those graft-modified with unsaturated carboxylic acids or their esters; polyesters; polyamides (including copolymerized polyamides); polyvinyl chloride; polyvinylidene chloride; acrylic resins; polystyrene; polyvinyl esters; polyester elastomers; polyurethane elastomers; chlorinated polystyrene; chlorinated polypropylene; aromatic polyketones or aliphatic polyketones, and polyalcohols obtained by reducing these; polyacetals; and polycarbonates. Among these, polyolefins are preferred from the viewpoint of excellent heat sealability and recyclability, and polyethylene and polypropylene are more preferred. As polyethylene, at least one type selected from the group consisting of polyethylenes such as linear low-density polyethylene, low-density polyethylene, and high-density polyethylene is preferred.
[0106] The thermoplastic resin content in the thermoplastic resin layer (δ) is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 98% by mass or more. The thermoplastic resin layer (δ) may be substantially composed of thermoplastic resin only, or may be composed of thermoplastic resin only.
[0107] The melt flow rate (MFR) of the thermoplastic resin constituting the thermoplastic resin layer (δ), measured according to JIS K 7210:2014 at 190°C and a 2160g load, is preferably 0.10g / 10min to 10.0g / 10min, and more preferably 0.30g / 10min to 5.0g / 10min. When the MFR of the thermoplastic resin is within the above range, the film formation stability tends to be good.
[0108] The average thickness of the thermoplastic resin layer (δ) is preferably 5 μm to 200 μm, more preferably 7 μm to 100 μm, and even more preferably 10 μm to 50 μm, from the viewpoint of industrial productivity and mechanical properties. If there are multiple thermoplastic resin layers (δ), it may be preferable that their total thicknesses fall within the above range.
[0109] In the multilayer structure of the present invention, the thermoplastic resin layer (δ) may be a single layer or multiple layers.
[0110] [Other layers] Other layers that the multilayer structure of the present invention may have include a paper layer, an inorganic vapor-deposited layer, a metal foil layer, and the like. Furthermore, the multilayer structure of the present invention may also include a vapor-deposited layer. Such a vapor-deposited layer may be provided on each layer, for example, using a sealant layer (α), a substrate layer (β), and a thermoplastic resin layer (δ) as substrates. Known components used as vapor-deposited layers can be appropriately used as components constituting such a vapor-deposited layer.
[0111] An inorganic vapor-deposited layer can be formed by depositing inorganic materials. Examples of inorganic materials include metals (e.g., aluminum), metal oxides (e.g., silicon oxide, aluminum oxide), metal nitrides (e.g., silicon nitride), metal nitride oxides (e.g., silicon oxynitride), or metal carbidine nitrides (e.g., silicon carbonitride). Among these, inorganic vapor-deposited layers formed from aluminum, aluminum oxide, silicon oxide, magnesium oxide, or silicon nitride are preferred from the viewpoint of industrial productivity, with aluminum being more preferred.
[0112] Furthermore, even if it is an aluminum vapor-deposited layer, irreversible oxidation may occur, and it may contain some aluminum oxide.
[0113] The lower limit of the average thickness of the inorganic deposition layer is preferably 15 nm, more preferably 20 nm, even more preferably 30 nm, and particularly preferably 40 nm. The upper limit of the average thickness of the inorganic deposition layer is preferably 150 nm, more preferably 130 nm, and even more preferably 80 nm. By setting the average thickness of the inorganic deposition layer to above the lower limit, gas barrier properties can be improved. On the other hand, by setting the average thickness of the inorganic deposition layer to below the upper limit, heat bridging can be suppressed and the heat insulation effect can be improved.
[0114] The inorganic vapor-deposited layer can be provided by known methods.
[0115] [Layer structure, physical properties, etc.] Assuming that the layer structure of the multilayer structure of the present invention is such that " / / " is laminated via an adhesive layer or directly laminated, for example, (1) α / / β, (2) α / γ / δ / / β, (3) α / / ε / β (4) α / γ / δ / / ε / β These are some examples. Note that α is the sealant layer, β is the substrate layer, γ is the adhesive layer, δ is the thermoplastic resin layer, and ε is the inorganic vapor deposition layer.
[0116] For example, the "α / γ / δ" layer structure portion in (2) above may be formed as a multilayer film (base film) as described above. The multilayer film portion may or may not be stretched. When the multilayer film consisting of the "α / γ / δ" layer structure is stretched, the "α / γ / δ" layer structure portion in the vapor-deposited film is stretched as a single unit. Also, for example, in (4) above, the "α / γ / δ / ε / β" layer structure portion may be formed as a multilayer film, or only the "α / γ / δ" layer structure portion may be formed as a multilayer film, and a thermoplastic resin layer (δ) may be laminated thereto via a separate adhesive layer (γ).
[0117] Specific examples of the layer structure of the multilayer structure of the present invention include, for example, a two-layer structure of resin composition layer (sealant layer (α)) / / polyester layer (base layer (β)), a three-layer structure of resin composition layer (sealant layer (α)) / / inorganic vapor deposition layer / polyester layer (base layer (β)), and so on. By including an inorganic vapor deposition layer as another layer in the multilayer structure, the non-adsorption properties and gas barrier properties when used as a packaging bag or the like can be further enhanced. Furthermore, other specific multilayer structures include, for example, a resin composition layer (sealant layer (α)) / / polyamide layer (base layer (β)) / / polyester layer (base layer (β)), a resin composition layer (sealant layer (α)) / / polyamide layer (base layer (β)), and so on.
[0118] <Method for manufacturing multilayer structures> The method for manufacturing the multilayer structure of the present invention is not particularly limited, and known manufacturing methods for single-layer or multilayer films, such as extrusion, co-extrusion, dry lamination, extrusion coating, and co-extrusion coating, can be employed. Specifically, when the sealant layer (α) of the multilayer structure is one layer of the multilayer film, examples include a method of co-extruding the heat-sealable layer and the other layers, a method of extruding the heat-sealable layer onto the other layers, and a method of dry laminating a film made of the heat-sealable layer with a film made of the other layers. When the sealant layer (α) is one layer of the multilayer film, adhesives or adhesive resins can be used as needed during lamination. The heat-sealable layer or other layers formed from resin may be oriented by uniaxial or biaxial stretching.
[0119] The overall thickness of the multilayer structure can be set appropriately depending on the application. A total thickness of 10 μm or more is preferred, 13 μm or more is more preferred, and 15 μm or more is even more preferred. An overall thickness of 10 μm or more tends to improve industrial productivity. Furthermore, an overall thickness of 300 μm or less is preferred, 200 μm or less is more preferred, 100 μm or less is even more preferred, and 50 μm or less is particularly preferred. An overall thickness of 300 μm or less tends to improve industrial productivity.
[0120] The multilayer structure may be stretched. For example, if a multilayer film comprises at least a sealant layer (α), an adhesive layer (γ), and a thermoplastic resin layer (δ), the resulting multilayer structure may be formed by stretching at least the sealant layer (α), adhesive layer (γ), and thermoplastic resin layer (δ) together. The degree of stretching may be 3 to 12 times in terms of area in at least one axial direction, 4 to 10 times, or 5 to 8 times. When the stretching ratio is 3 times or more, the gas barrier properties tend to improve. On the other hand, when the stretching ratio is 12 times or less, the film surface tends to be good.
[0121] The multilayer film may be stretched in two axes as an area-based stretching ratio of 4 to 144 times, preferably 16 to 100 times, and more preferably 25 to 64 times. A stretching ratio of 9 times or more improves gas barrier properties. On the other hand, a stretching ratio of 144 times or less results in a good film surface.
[0122] The method for stretching a multilayer film is not particularly limited, and examples include tenter stretching, tubular stretching, and roll stretching. From the viewpoint of manufacturing cost, sequential biaxial stretching or simultaneous biaxial stretching by tenter stretching and tubular stretching is preferred. From the viewpoint of equipment cost, uniaxial stretching by roll stretching is preferred. Furthermore, if the multilayer film is an inflation-molded product, roll stretching is preferred from the viewpoint that the folded cylindrical multilayer film after inflation molding can be easily stretched in the uniaxial direction.
[0123] The difference in oxygen permeability measured at 30°C and 65%RH between the widthwise ends and the center of the multilayer structure is preferably less than 15%, more preferably less than 10%, even more preferably less than 5%, and most preferably less than 1%. Having the difference in oxygen permeability of the multilayer structure below the above upper limit allows for a longer period during which the oxygen concentration in the internal space of a bag or the like formed by the packaging material containing the multilayer structure can be kept low. Here, oxygen permeability (mL / m³)2 (Day·atm) is defined as the amount of oxygen (mL) that permeates a multilayer structure over an area (m²). 2 This refers to the value obtained by dividing the oxygen permeability by the permeation time (days) and the difference (atm) between the oxygen gas pressure on one side and the oxygen gas pressure on the other side. Specifically, if the oxygen permeability is, for example, "5 mL / m³", then this value is obtained by dividing the oxygen permeability by the permeation time (days) and the difference (atm) between the oxygen gas pressure on one side and the oxygen gas pressure on the other side. 2 If the pressure difference of the oxygen gas is less than 1 atmosphere, then 1 meter of film per day. 2 This indicates that 5 mL of oxygen permeates through the material. Furthermore, the difference in oxygen permeability in the width direction of the above multilayer structure can be considered equivalent to the difference in oxygen permeability in the width direction of the single-layer film of the sealant layer (α).
[0124] The lower limit of the volatile content in the sealant layer (α) is not particularly limited, but is preferably 0.01% by mass, more preferably 0.03% by mass, and still more preferably 0.05% by mass. The upper limit of the volatile content is preferably 1.1% by mass, more preferably 0.5% by mass, and still more preferably 0.3% by mass.
[0125] However, when applying the multilayer structure to a vacuum insulation material, it is preferable that the volatile content in the multilayer structure be as small as possible. This is because volatile components generated from the multilayer structure may penetrate the vacuum portion of the vacuum insulation material, potentially reducing the vacuum level inside the vacuum insulation material and thus degrading its insulation performance.
[0126] Here, the volatile content can be determined from the mass change before and after drying at 105°C for 3 hours using the following formula. Volatile content (mass%) = [(mass before drying - mass after drying) / mass after drying] × 100
[0127] In the multilayer structure, it is preferable that the heat seal strength measured in accordance with JIS Z1707 (2019) when the sealant layers (α) of the multilayer structure are pressed together for 1 second using a hot plate type heat sealer at a temperature of 200°C and a pressure of 0.1 MPa is 20 N / 15 mm or more. A heat seal strength of 20 N / 15 mm or more results in good gas barrier properties as a packaging material. The heat seal strength is preferably 23 N / 15 mm or more, and more preferably 26 N / 15 mm or more. The heat seal strength may also be 50 N / 15 mm or less, 40 N / 15 mm or less, or 35 N / 15 mm or less.
[0128] The method for heat-sealing the multilayer structure is not particularly limited as long as the sealant layers (α) are heat-sealed to each other, and known methods can be used. Examples include heat-sealing using a hot plate heat sealer, impulse sealer, ultrasonic sealer, friction heat sealer, dielectric heat sealer, etc. The temperature during heat sealing is preferably above the melting point of the heat-fused layer and below the melting point + 30°C from the viewpoint of heat seal strength and prevention of appearance defects. The heat-sealing pressure is preferably between 0.01 MPa and 1.0 MPa from the viewpoint of heat seal strength and prevention of appearance defects. The heat-sealing time is preferably between 0.05 seconds and 5 seconds from the viewpoint of heat seal strength and productivity.
[0129] [Application] The multilayer structure of the present invention exhibits high uniformity of gas barrier properties in the heat-seal layer (α), high heat-seal strength, and a good appearance after heat-sealing. Therefore, this multilayer structure can be applied to a variety of uses. Examples of applications for this multilayer structure include various packaging materials such as food packaging, pharmaceutical packaging, industrial chemical packaging, and pesticide packaging, as well as vacuum insulation materials.
[0130] <Packaging material> The packaging material of the present invention comprises the multilayer structure of the present invention. The packaging material of the present invention is formed, for example, by secondary processing of the multilayer structure of the present invention, or a multilayer structure comprising the same. The packaging material has excellent gas barrier properties due to its multilayer structure. In the packaging material of the present invention, the sealant layer (α) of the multilayer structure of the present invention constitutes the inner surface of the packaging material; that is, the packaging material is manufactured by heat-sealing the sealant layers (α) of the multilayer structure together. Since the sealant layer (α) has the property of being less adsorbent of compounds, etc. (non-adsorbent), the packaging material of the present invention is less likely to adsorb the components of the contents, and can be suitably used as packaging for foods, beverages, luxury goods, pharmaceuticals, cosmetics, fragrances, toiletries, etc., that contain fragrance components or medicinal components.
[0131] The packaging material of the present invention can be formed into various forms depending on the application, such as vertically formed, filled, and sealed bags, vacuum packaging bags, pouches with spouts, laminated tube containers, container lids, etc.
[0132] [Vertical-shaped bag, filled, and sealed] Vertically constructed, filled, and sealed bags are used to package foods, beverages, and other products in the form of liquids, viscous materials, powders, solid bulk materials, or combinations thereof.
[0133] Vertically formed sealed bags are created by heat-sealing a sealant layer (α) of a multilayer structure. When heat sealing is performed, it is usually necessary to place the sealant layer (α) in the layer that will be the inside of the vertically formed sealed bag in the multilayer structure.
[0134] For vertically formed, filled, and sealed bags, a base layer (β) / / sealant layer (α) is preferred.
[0135] As described above, the packaging material of the present invention has excellent gas barrier properties, and therefore, in the case of a vertically formed, filled, and sealed bag, which is an example of this packaging material, the deterioration of the quality of the contents can be suppressed over a long period of time.
[0136] [Vacuum packaging bag] Vacuum packaging bags are used for applications where vacuum packaging is desired, such as the preservation of food and beverages. Preferred layer configurations for vacuum packaging bags are polyamide layer (base layer (β)) / / base layer (β) / / sealant layer (α) and polyamide layer (base layer (β)) / / sealant layer (α). Such vacuum packaging bags, due to the presence of the sealant layer (α), exhibit particularly excellent gas barrier properties and non-adsorption properties after vacuum packaging.
[0137] [Pouch with spout] Spouted pouches are used to package liquid substances such as soft drinks, jelly drinks, yogurt, fruit sauces, seasonings, functional water, and liquid foods. A preferred layer structure for these spouted pouches is a polyamide layer (base layer (β)) / / sealant layer (α). Because of this multilayer structure, such spouted pouches exhibit excellent gas barrier properties and non-adsorption. Therefore, spouted pouches can prevent deterioration of the contents and maintain their aroma even after transportation and long-term storage.
[0138] [Laminated tube container] Laminated tube containers are used, for example, to package cosmetics, pharmaceuticals, food products, toothpaste, etc. A preferred layer structure for these laminated tube containers is a polyamide layer (base layer (β)) / / sealant layer (α). Such laminated tube containers, due to their multilayer structure, exhibit excellent gas barrier properties and fragrance retention.
[0139] [Container lid material] The container lid material is used for containers filled with foods such as processed meat products, processed vegetables, processed seafood products, and fruits. A preferred layer structure for this container lid material is a polyamide layer (base layer (β)) / / sealant layer (α). Because such a container lid material has this multilayer structure, it exhibits excellent gas barrier properties and aroma retention, thus suppressing the deterioration of the food contents over a long period of time.
[0140] <Vacuum insulation material> The vacuum insulation body of the present invention comprises the multilayer structure of the present invention. The vacuum insulation body is used in applications requiring cooling or heating. Examples of such vacuum insulation bodies include those in which a core material such as glass wool is sealed in a vacuum within an outer packaging material. The outer packaging material preferably includes at least one inorganic vapor-deposited layer of the multilayer structure of the present invention, and is formed by heat sealing such a multilayer structure.
[0141] There are no particular restrictions on the number of layers or the stacking order in the outer packaging material, but it is preferable to include an inorganic vapor-deposited layer. Preferred layer configurations for the outer packaging material are polyamide layer (base layer (β)) / / base layer (β) / inorganic vapor-deposited layer / / sealant layer (α) and polyamide layer (base layer (β)) / inorganic vapor-deposited layer / / base layer (β) / / sealant layer (α).
[0142] Such vacuum insulation materials exhibit excellent gas barrier properties because their outer packaging material incorporates the multilayer structure of the present invention. Therefore, since these vacuum insulation materials can maintain their insulating effect over a long period of time, they can be used as insulating materials for home appliances such as refrigerators, water heaters, and rice cookers; as insulating materials for residential use in walls, ceilings, attics, floors, etc.; as roofing materials for vehicles; and as insulating panels for vending machines, etc. [Examples]
[0143] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.
[0144] [Evaluation Method] (1) Measurement of ethylene unit content, degree of saponification, and amount of epoxypropane modification (amount of modification relative to total vinyl alcohol units) The crude dried EVOH obtained in the synthesis example was dried in a vacuum dryer at 120°C for 12 hours. The vacuum-dried EVOH was dissolved in deuterated dimethyl sulfoxide (DMSO-d6) containing tetramethylsilane (TMS) as an internal standard and trifluoroacetic acid (TFA) as an additive, and heated at 500 MHz. 1Measurements were performed at 80°C using 1H-NMR (GX-500, JEOL Ltd.), and the ethylene unit content and degree of saponification were determined from the peak intensity ratios of ethylene units, vinyl alcohol units, and vinyl ester units. When measuring the EVOH pellets obtained in Synthesis Examples 9 and 10, measurements were performed without vacuum drying, and the amount of modification relative to the total vinyl alcohol units was simultaneously calculated from the peak intensity of the epoxypropane-modified vinyl alcohol units. In the EVOH (A9, A10) obtained in Synthesis Examples 9 and 10, the amount of epoxypropane modification relative to the total vinyl alcohol units is equal to the content of structural unit (x) relative to the total vinyl alcohol units.
[0145] (2) Sodium ion content, phosphoric acid content and boric acid content 0.5 g of the dried resin composition pellets obtained in the Reference Example, Reference Comparative Example, Example, and Comparative Example were placed in a Teflon® pressure vessel, and 5 mL of concentrated nitric acid was added to decompose it at room temperature for 30 minutes. After 30 minutes, the lid was closed, and the decomposition was carried out by heating at 150°C for 10 minutes, then at 180°C for 5 minutes, using a wet decomposition apparatus (Actac Co., Ltd. "MWS-2"), and then cooled to room temperature. This processed solution was transferred to a 50 mL volumetric flask (TPX®) and diluted with pure water. The metal content of this solution was analyzed using an ICP emission spectrometer (PerkinElmer "OPTIMA4300DV"), and the content of sodium ions (element sodium), phosphoric acid, and boric acid was measured. The phosphoric acid content was calculated as a phosphate root equivalent, and the boric acid content was calculated as an orthoboric acid equivalent. Calibration curves prepared using commercially available standard solutions were used for quantification.
[0146] (3) Acetic acid content 20 g of dried resin composition pellets obtained in the Reference Example, Reference Comparative Example, Example, and Comparative Example were placed in 100 mL of deionized water and heated at 95°C for 6 hours for extraction. The extract was neutralized and titrated with 1 / 50 N NaOH using phenolphthalein as an indicator to quantify the acetic acid content.
[0147] (4) Melt Flow Rate (MFR) The dried resin composition pellets obtained in the reference example and reference comparative example were filled into a 9.55 mm inner diameter, 162 mm long cylinder of a melt indexer L244 (manufactured by Takara Kogyo Co., Ltd.), melted at 210°C, and then a uniform load was applied to the molten resin composition using a plunger with a mass of 2,160 g and a diameter of 9.48 mm. The amount of resin composition extruded per unit time (g / 10 min) through a 2.1 mm diameter orifice located in the center of the cylinder was measured and defined as the MFR (Metal Flow Rate).
[0148] (5) Determination of crotonaldehyde, 2,4-hexadienal and 2,4,6-octatrienal Samples were prepared by freeze-pulverizing 0.50 g of dried resin composition pellets obtained in the Reference Example, Reference Comparative Example, Example, and Comparative Example, and weighing 50.0 mg of the resulting sample into a glass tube for a thermal desorption gas chromatograph mass spectrometer. Using the thermal desorption gas chromatograph mass spectrometer described below, the sample was heated under the conditions described below to adsorb the volatile gas from the sample into an adsorption tube. The gas re-released from the adsorption tube was then separated by a column, and the peaks for each component were detected. Calibration curves were created from the peak areas of standard samples of crotonaldehyde, 2,4-hexadienal, and 2,4,6-octatrienal, and each component was quantified using the absolute calibration curve method. When measuring the standard sample, the standard sample was impregnated into an adsorption tube (manufactured by Tenax® / Carboxen®), and the adsorption tube impregnated with the standard sample was used instead of the sample tube. The temperature at which the sample was released after adsorption was changed from the sample tube temperature of 170°C to the adsorption tube temperature of 260°C, but the measurement was performed in the same manner as when measuring the sample tube. (Heating desorption section) Device: TurboMatrix-ATD (manufactured by PerkinElmer Japan) Temperature when adsorbing the sample onto the adsorption tube: 170°C (sample tube), -30°C (adsorption tube), 250°C (valve), 260°C (transfer line) Adsorption time to the adsorption tube: 10 minutes Temperature during release after sample adsorption: 170°C (sample tube), 260°C (adsorption tube), 250°C (valve), 260°C (transfer line) Adsorption tube release time: 35 minutes Carrier gas: Helium Flow rate of carrier gas into the column: 1.0 ml / min Pressure: 120kPa (Gas Chromatography and Mass Spectrometry Department) Equipment: 7890B GC System, 7977B MSD (manufactured by Agilent Technologies) Column: DB-WAX UI (Length: 30m, Inner diameter: 0.25mm, Film thickness: 0.50μm) Column oven temperature: Hold at 40°C for 5 minutes, then raise the temperature to 240°C at a rate of 10°C / min, and hold for 10 minutes (total measurement time: 35 minutes). Transfer line (connection point) temperature: 240℃ Ionization conditions: EI+ Detection ion mass range: m / z = 29-600 Detection method: SCAN (Standard sample) Crotonaldehyde: Manufactured by Aldrich. 2,4-Hexadienal: Manufactured by Aldrich. 2,4,6-Octatrienal: Manufactured by Nerd Research Institute
[0149] (6) Determination of sorbic acid and myrcene The dried resin composition pellets obtained in the Reference Example, Reference Comparative Example, Example, and Comparative Example were freeze-dried and pulverized. 22 g of the pulverized material was loaded into a Soxhlet extractor and extracted with 100 mL of chloroform for 16 hours. The amounts of sorbic acid and myrcene in the resulting chloroform extract were quantitatively analyzed by high-performance liquid chromatography to determine the content of sorbic acid and myrcene in the resin composition. A calibration curve prepared using sorbic acid and myrcene standards was used for the quantification.
[0150] (7) Dybuild-up evaluation The dried resin composition pellets obtained in the Reference Example, Reference Comparative Example, Example, and Comparative Example were extruded from an extruder under the following conditions. After 60 minutes, the die buildup (die lip) around the die was visually inspected and evaluated according to the following criteria. In cases A to D, it was determined that die buildup was suppressed. (Extruder conditions) • Equipment: 20mmφ single-screw extruder (D2020, manufactured by Toyo Seiki Seisakusho Co., Ltd.) L / D:20 • Screw: Full Flight Screen mesh: 50 mesh / 100 mesh / 50 mesh • Die: φ1mm, 1 hole ·Setting temperature: C1 / C2 / C3 / D=180℃ / 220℃ / 220℃ / 220℃ ·Discharge amount: 1.44kg / h • Rotation speed: 100 rpm (Evaluation: Judgment Criteria) A (Good): No eye discharge. B (Fairly good): Very slight amount of eye discharge. C (Acceptable): A small amount of eye discharge is present. D (Slightly Poor): Clear eye discharge is present. E (Defective): Large particles of eye discharge are attached all around the die hole.
[0151] (8) Hue evaluation The Yellow Index (YI) values of the dried resin composition pellets obtained in the Reference Example, Reference Comparative Example, Example, and Comparative Example were measured and calculated using a Hunter LAB Scan XE in accordance with JIS K7373:2006. A smaller value indicates suppressed yellowing and superior hue.
[0152] (9) Evaluation of neck-in resistance during film formation Using the dried resin composition pellets obtained in the Reference Example, Reference Comparative Example, Example, and Comparative Example, the resin composition was extruded from a single-screw extruder under the following conditions. Ten minutes after feeding the dried resin composition pellets, the width of the molten resin (melt curtain) discharged from the T-die was measured at a position 100 mm from the lip (T-die discharge port). The width of the molten resin was evaluated according to the following criteria. In cases A to C, it was determined that neck-in was suppressed. (Extruder conditions) • Extruder: L / D=26, 40mmφ single-screw extruder • Screw: Full Flight • Screw rotation speed: 50 rpm Screen mesh: 50 mesh / 100 mesh / 50 mesh • Die shape: T-shaped, lip width 550mm, lip spacing 0.7mm ·Setting temperature: C1 / C2 / C3 / D=170℃ / 240℃ / 260℃ / 260℃ (Evaluation: Judgment Criteria) A (Good): More than 85% of the lip width B (Fairly Good): 82.5% to less than 85% of lip width C (Slightly Poor): Lip width is between 80% and 82.5% D (Defective): Less than 80% of the lip width
[0153] (10) Melting point measurement The crudely dried EVOH obtained in the synthesis examples was dried in a vacuum dryer at 120°C for 12 hours. The vacuum-dried EVOH was heated from 30°C to 250°C at a rate of 10°C / min using a differential scanning calorimeter "Q2000" manufactured by TA Instruments. After cooling at a rate of 50°C / min, the melting point was determined from the peak temperature measured by the secondary heating. Note that the EVOH pellets obtained in synthesis examples 9 and 10 were measured without vacuum drying.
[0154] (11) Measurement of oxygen permeability (OTR) <Conditions for creating single-layer film> The dried resin composition pellets obtained in the reference example and reference comparative example were used to form films under the following conditions, yielding single-layer films with an average thickness of 30 μm. (Extruder conditions) ·L / D: 26, 40 mmφ single-screw extruder ·Screw: Full flight ·Screw rotation speed: 30 rpm ·Screen mesh: 50 mesh / 100 mesh / 50 mesh ·Die shape: T-type, lip width 550 mm, lip gap 0.7 mm ·Set temperature: C1 / C2 / C3 / D = 170°C / 230°C / 230°C / 230°C ·Take-up roll temperature: 80°C ·Take-up roll speed: 10 to 11 m / min <OTR (Oxygen Transmission Rate) Measurement> For the obtained 30 μm-thick single-layer film, a circular sample with a diameter of 90 mm was cut out centered on the center in the width direction, conditioned at 30°C and 65%RH, and then an oxygen transmission rate measuring device ("OX-Tran 2 / 20" from ModernControl, lower detection limit 0.01 mL / (m 2 ·day·atm)) was used to measure the oxygen transmission rate at 30°C and 65%RH in accordance with ISO 14663-2 annex C. The oxygen transmission rate of the single-layer films or multilayer films obtained in Examples and Comparative Examples was also measured by the same method.
[0155] (12) Width direction uniformity of OTR For the single-layer film or multilayer film used in the measurement of (11), a circular sample with a diameter of 90 mm was cut out centered at a position 70 mm from the film edge, and the OTR was measured under the same conditions as in (11). The difference from the OTR of the center sample was calculated, and the magnitude of the difference was evaluated on a three-grade scale of A to C. (Evaluation: Judgment criteria) A: Difference is less than 10% B: Difference is 10% or more and less than 15% C: Difference is 15% or more
[0156] (13) Heat seal strength and appearance For the multilayer structures obtained in the examples and comparative examples, a heat-seal layer (α) was superimposed and pressed together for 1 second at a temperature of 200°C and a pressure of 0.1 MPa using a hot plate type heat sealer (HBS-280 bag sealer manufactured by Hirai Shoji Co., Ltd.). The heat seal strength (N / 15mm) per 15mm width of the heat-sealed film was measured using a tensile testing machine according to the method described in JIS Z 1707 (2019). The tensile speed during the seal strength measurement was 300 mm / min.
[0157] Furthermore, the appearance of the heat-sealed portion was visually evaluated according to the following criteria. A rating of C indicates that the deterioration of the appearance after heat sealing was not suppressed. A: Has an excellent appearance B: Slight thinning and foaming have occurred, resulting in a somewhat poor appearance. C: Poor appearance, such as noticeable thinning or foaming.
[0158] <Synthesis Example 1> In a 200L pressurized reactor equipped with a jacket, stirrer, nitrogen inlet, ethylene inlet, and initiator addition port, 75.0 kg of vinyl acetate (hereinafter sometimes referred to as VAc) and 7.2 kg of methanol (hereinafter sometimes referred to as MeOH) were charged, and the reactor was purged with nitrogen by bubbling with nitrogen for 30 minutes. Next, after adjusting the temperature inside the reactor to 65°C, ethylene was introduced so that the reactor pressure (ethylene pressure) reached 4.13 MPa, and 9.4 g of 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., "V-65") was added as a polymerization initiator to start polymerization. During polymerization, the ethylene pressure was maintained at 4.13 MPa and the polymerization temperature at 65°C. After 4 hours, when the conversion rate of VAc (polymerization rate based on VAc) reached 49.7%, the reactor was cooled, and a solution of 0.2 g of copper acetate dissolved in 20 kg of methanol was added to the container to stop the polymerization. After opening the reaction vessel and removing the ethylene, nitrogen gas was bubbled through to completely remove the ethylene. Next, the polymerization solution was withdrawn from the container and diluted with 20 L of MeOH. This solution was fed from the top of a column-type container, and MeOH vapor was fed from the bottom of the column to remove any unreacted monomers remaining in the polymerization solution along with the MeOH vapor, thereby obtaining an MeOH solution of ethylene-vinyl acetate copolymer (hereinafter sometimes referred to as EVAc).
[0159] Next, 150 kg of a 20% by mass MeOH solution of EVAc was charged into a 300 L reaction vessel equipped with a jacket, stirrer, nitrogen inlet, reflux condenser, and solution addition port. The temperature of this solution was raised to 60°C while blowing nitrogen gas into it, and a 2 N sodium hydroxide MeOH solution was added at a rate of 450 mL / min for 2 hours. After the addition of the sodium hydroxide MeOH solution was completed, the temperature in the system was maintained at 60°C, and the saponification reaction was allowed to proceed by stirring for 2 hours while draining the MeOH and methyl acetate produced in the saponification reaction out of the reaction vessel. After that, 8.7 kg of acetic acid was added to stop the saponification reaction.
[0160] Subsequently, while heating and stirring at 80°C, 120 L of deionized water was added to drain MeOH from the reaction vessel and precipitate EVOH. The EVOH precipitated by decantation was collected and pulverized using a pulverizer. The obtained EVOH powder was placed in a 1 g / L aqueous acetic acid solution (bath ratio 20: 20 L of aqueous solution per 1 kg of powder) and stirred and washed for 2 hours. This was then dehydrated and placed in another 1 g / L aqueous acetic acid solution (bath ratio 20) and stirred and washed for 2 hours. The dehydrated mixture was then placed in deionized water (bath ratio 20), stirred and washed for 2 hours, and dehydrated. This process was repeated three times to purify the EVOH. The electrical conductivity of the washing solution was 3 μS / cm (measured with "CM-30ET" from Toa Denpa Kogyo Co., Ltd.). Next, the purified product was immersed in 250 L of an aqueous solution containing 0.5 g / L of acetic acid and 0.1 g / L of sodium acetate for 4 hours with stirring, then drained, and dried at 60°C for 16 hours to obtain 16.1 kg of crude dried EVOH.
[0161] The above procedure for synthesizing EVOH was repeated to obtain 15.9 kg of crude dried EVOH, resulting in a total of 32.0 kg of crude dried EVOH(A1). The ethylene unit content, degree of saponification, and melting point of the crude dried EVOH(A1) were measured according to the methods described in evaluation methods (1) and (10) above. The results are shown in Table 2.
[0162] <Synthesis Examples 2-8> The size of the pressurized reaction vessel, the amounts of VAc and MeOH charged, the ethylene pressure, the amount of polymerization initiator added, the temperature inside the reaction vessel (temperature during polymerization), the reaction time, the conversion rate of VAc, the amount of EVAc MeOH solution charged in the saponification step, and the rate of addition of sodium hydroxide MeOH solution are as shown in Table 1. Except that the synthesis was performed only once, the crude dried products of each EVOH(A2) to EVOH(A8) were obtained in the same manner as in Synthesis Example 1. The ethylene unit content, degree of saponification, and melting point of the crude dried products of EVOH(A2) to EVOH(A8) were measured according to the methods described in Evaluation Methods (1) and (10) above. The results are shown in Table 2.
[0163] <Synthesis Example 9> Using the apparatus described in paragraph
[0158] and Figure 1 of Japanese Patent Publication No. 2003-231715, EVOH(A9) pellets were prepared by the following procedure. A TEM-35BS extruder (37 mmφ, L / D=52.5) manufactured by Toshiba Machine Co., Ltd. was used. Barrel C1 was water-cooled, barrels C2-C3 were set to 200°C, and barrels C4-C15 were set to 240°C, and the extruder was operated at a screw rotation speed of 400 rpm. Dry resin composition pellets obtained in Reference Example 38, described later, were fed through the resin feed port of C1 and melted. After that, water and oxygen were removed from vent 1, and epoxypropane was fed as a modifying agent 2 through the hydraulic inlet of C9. Then, unreacted epoxypropane was removed from vent 2, pelletized, and hot-air dried at 80°C for 2 hours to obtain 8 mol% modified EVOH(A9) pellets. The obtained EVOH(A9) pellets were measured for ethylene unit content, degree of saponification, epoxypropane modification amount (amount relative to total vinyl alcohol units), and melting point according to the methods described in evaluation methods (1) and (10) above. The results for ethylene unit content, degree of saponification, and melting point are shown in Table 2. The epoxypropane modification amount (content of structural units (x) relative to total vinyl alcohol units) was 8 mol%.
[0164] <Synthesis Example 10> Except for changing the dry resin composition pellets fed as raw material to the dry resin composition pellets obtained in Reference Example 43, the pellets were pelletized in the same manner as in Synthesis Example 9 to obtain 8 mol% modified EVOH(A10) pellets. The ethylene unit content, degree of saponification, amount of epoxypropane modification (amount relative to total vinyl alcohol units), and melting point of the obtained EVOH(A10) pellets were measured according to the methods described in Evaluation Methods (1) and (10) above. The results for ethylene unit content, degree of saponification, and melting point are shown in Table 2. The amount of epoxypropane modification (content of structural units (x) relative to total vinyl alcohol units) was 8 mol%.
[0165] [Table 1]
[0166] [Table 2]
[0167] <Reference example 1> In a 60L stirring tank equipped with a jacket, stirrer, and reflux condenser, 2 kg of the crudely dried EVOH(A1) obtained in Synthesis Example 1, 0.8 kg of water, and 2.2 kg of MeOH were charged and stirred at 60°C for 5 hours until completely dissolved. Sorbic acid, crotonaldehyde, 2,4-hexadienal, and 2,4,6-octatrienal were added to the resulting solution. This solution was extruded through a 4 mm diameter gold plate into a water / MeOH = 90 / 10 mixture cooled to -5°C to precipitate in strand form, and these strands were cut into pellets with a strand cutter to obtain hydrated EVOH pellets. The moisture content of the obtained hydrated EVOH pellets was measured using a Mettler halogen moisture meter "HR73" and was found to be 52% by mass.
[0168] The obtained hydrated EVOH pellets were placed in a 1 g / L aqueous acetic acid solution (bath ratio 20) and stirred and washed for 2 hours. After desaturation, the pellets were placed again in a 1 g / L aqueous acetic acid solution (bath ratio 20) and stirred and washed for 2 hours. After desaturation, the aqueous acetic acid solution was replaced and the same procedure was repeated. The pellets washed in aqueous acetic acid solution and then desaturated were placed in deionized water (bath ratio 20) and stirred and washed for 2 hours, and desaturated. This process was repeated three times until the electrical conductivity of the washing solution was 3 μS / cm or less (measured with Toa Denpa Kogyo Co., Ltd.'s "CM-30ET"), thereby obtaining hydrated EVOH pellets from which the catalyst residue from the saponification reaction had been removed.
[0169] The obtained water-containing pellets were placed in an aqueous solution (bath ratio 20) with a sodium acetate concentration of 0.510 g / L, an acetic acid concentration of 0.8 g / L, and a phosphoric acid concentration of 0.04 g / L, and immersed for 4 hours with periodic stirring to perform chemical treatment. These pellets were dehydrated and dried at 80°C for 3 hours and at 105°C for 16 hours under a nitrogen stream with an oxygen concentration of 1 vol% or less to obtain cylindrical (average diameter 2.8 mm, average height 3.2 mm) dried resin composition pellets containing EVOH(A1), acetic acid, phosphoric acid, sodium ions (sodium salt), crotonaldehyde, 2,4-hexadienal, 2,4,6-octatrienal, and sorbic acid. The obtained dried resin composition pellets were evaluated according to the methods described in evaluation methods (2) to (9) above. The sodium ion content in the dried resin composition pellets was 100 ppm, the phosphoric acid content was 40 ppm (calculated as phosphate root), and the acetic acid content was 200 ppm. The content of each component other than EVOH is based on the EVOH content. Other evaluation results are shown in Table 3. The amounts of each component added were adjusted so that the content of crotonaldehyde, 2,4-hexadienal, 2,4,6-octatrienal, and sorbic acid were as shown in Table 3.
[0170] <Reference Examples 2~61, Reference Comparative Examples 1~4, 6~24> Dry resin composition pellets were prepared and evaluated in the same manner as in Reference Example 1, except that the types of EVOH (A), unsaturated aliphatic aldehydes (B), conjugated polyene compounds (C), and boric acid content were adjusted to match those shown in Tables 3 to 10. For the 800 ppm boric acid content, an aqueous solution containing sodium acetate, etc. (bath ratio 20) was prepared to a boric acid concentration of 0.25 g / L. For the 1800 ppm boric acid content, an aqueous solution containing sodium acetate, etc. (bath ratio 20) was prepared to a boric acid concentration of 0.57 g / L. The sodium ion content of EVOH in each dry resin composition pellet was 100 ppm, the phosphoric acid content was 40 ppm (based on phosphate root), and the acetic acid content was 200 ppm. Other evaluation results are shown in Tables 3 to 10. The content of each component other than EVOH is based on the EVOH content.
[0171] <Reference Example 5> Dry resin composition pellets were prepared and evaluated in the same manner as in Reference Example 1, except that crotonaldehyde, 2,4-hexadienal, and 2,4,6-octatrienal were not added, and the catalyst residue from the saponification reaction had been removed. The hydrated EVOH pellets were placed in methanol (bath ratio 10), stirred and washed for 2 hours, and dehydrated. This process was repeated twice, and the resulting pellets were placed in ion-exchanged water (bath ratio 20), stirred and washed for 2 hours, and dehydrated. This process was repeated three times. The sodium ion content in the dry resin composition pellets was 100 ppm, the phosphoric acid content was 40 ppm (based on phosphate root), and the acetic acid content was 200 ppm. The content of each component other than EVOH is based on the EVOH content. Other evaluation results are shown in Table 3. The content of crotonaldehyde, 2,4-hexadienal, 2,4,6-octatrienal, and sorbic acid was below the detection limit.
[0172] [Table 3]
[0173] [Table 4]
[0174] [Table 5]
[0175] [Table 6]
[0176] [Table 7]
[0177] [Table 8]
[0178] [Table 9]
[0179] [Table 10]
[0180] From the reference examples and reference comparison examples, it can be seen that when b1 / (b2+b3) is between 2.0 and less than 150.0, neck-in resistance is good, the smaller b1+b2+b3 is, the lower the YI, the lower the content of the conjugated polyene compound (C) c, the lower the YI, and when b2+2b3 is 0.65 ppm or less, die build-up is suppressed.
[0181] A more detailed examination based on Table 3 reveals the following: Reference Comparative Example 5, which does not contain unsaturated aliphatic aldehyde (B), and Reference Comparative Examples 1-3 and 6-9, which contain various unsaturated aliphatic aldehydes (B) individually, do not suppress neck-in. Similarly, Reference Comparative Example 10, where the value of b1 / (b2+b3) is less than 2.0, also does not suppress neck-in. On the other hand, as can be seen from the reference examples, neck-in is suppressed when the value of b1 / (b2+b3) is in the range of 2.0 or more and less than 150.0, and in particular, neck-in is most suppressed when the value of b1 / (b2+b3) is around 10 (for example, 8.0 or more and 13.0 or less), as in Reference Examples 4, 5, 13, 14, 21, and 24. Furthermore, in Comparative Example 4, where b2+2b3 exceeds 0.65 ppm, dye buildup is not suppressed, whereas, as can be seen from the reference examples, when b2+2b3 is 0.65 ppm or less, dye buildup is suppressed, and in particular, when b2+2b3 is 0.10 ppm or less, dye buildup is suppressed more effectively. In addition, regarding the total content of crotonaldehyde (B1), 2,4-hexadienal (B2), and 2,4,6-octatrienal (B3), b1+b2+b3, as can be seen from Comparative Example 4, Reference Examples 1-7, 12-26, etc., it can be seen that the lower the total content, the better the hue. Furthermore, from Reference Examples 6, 9-11, it can be seen that a smaller content of conjugated polyene compounds results in better hue.
[0182] <Example 1> The dried resin composition pellets (resin composition) obtained in Reference Example 5 were melted at 240°C in a single-screw extruder and extruded from the die onto a casting roll. Simultaneously, air was blown onto the extruded film at a wind speed of 30 m / s using an air knife to obtain a single-layer film (sealant layer (α)) with a thickness of 30 μm. The OTR of the obtained single-layer film was measured according to the method described in Evaluation Method (11) above. The results are shown in Table 12. A multilayer structure of sealant layer (α) / adhesive layer (γ) / base layer (β) was fabricated by laminating a 12 μm thick PET film (PET12) as a base layer (β) using an adhesive on the obtained single-layer film. When laminating the base layer (β), a two-component urethane adhesive ("Takelac A-520" and "Takenate A-50" manufactured by Mitsui Chemicals, Inc.) was applied to provide an adhesive layer (γ) with a dry thickness of 2 μm, and the layers were laminated by the dry lamination method. The heat seal strength and appearance of the obtained multilayer structure were evaluated using the method described in evaluation method (13) above, and the results are shown in Table 12. The other evaluation results for the dried resin composition pellets used in Reference Example 5 are reproduced in Tables 11 and 12.
[0183] <Examples 2-8, Comparative Examples 1 and 2> Single-layer films and multilayer structures were prepared and evaluated in the same manner as in Example 1, except that the dried resin composition pellets obtained in Reference Examples 28, 38, 43, 48, 2, 7, Synthesis Example 10, and Reference Comparative Examples 4 and 3 were used. The results are shown in Table 12. The other evaluation results for the dried resin composition pellets of the Reference Examples or Reference Comparative Examples used are also listed again in Tables 11 and 12. The dried resin composition pellet of EVOH obtained in Synthesis Example 10 (A10) was evaluated according to the methods described in evaluation methods (5) to (12) above. The evaluation results are shown in Tables 11 and 12.
[0184] <Example 9> The dried resin composition pellets (resin composition) obtained in Reference Example 5 were melted at 240°C in a uniscrew extruder and extruded from the die onto a casting roll. Simultaneously, air was blown onto the pellets using an air knife at a wind speed of 30 m / s to obtain an unstretched film with a thickness of 170 μm. The obtained 170 μm thick unstretched film was brought into contact with 80°C hot water for 10 seconds, stretched 3.2 times in the longitudinal direction and 3.0 times in the transverse direction using a tenter-type simultaneous biaxial stretcher in a 90°C atmosphere, and then heat-treated for 5 seconds in a tenter set to 170°C. The film edges were then cut to obtain a biaxially stretched single-layer film (sealant layer (α)) with a thickness of 12 μm. A multilayer structure was fabricated and evaluated in the same manner as in Example 1, except that the obtained sealant layer (α) was used. The results are shown in Table 12. The other evaluation results for the dried resin composition pellets used are also reproduced in Tables 11 and 12.
[0185] [Table 11]
[0186] [Table 12]
[0187] <Example 10> Using the dried resin composition pellets (resin composition) obtained in Reference Example 5, a cylindrical multilayer film was fabricated using an inflation extrusion molding machine under the following conditions. Note that three thermoplastic resin layers (δ) with a thickness of 30 μm were laminated, resulting in a single thermoplastic resin layer (δ) with a thickness of 90 μm. (Multilayer film fabrication conditions) Layer composition of the multilayer structure: [Outer side] Thermoplastic resin layer (δ) / Adhesive layer (γ) / Sealant layer (α) [Inner side] = 90 μm / 20 μm / 30 μm (Total thickness 140 μm) Thermoplastic resin layer (δ): δ-1 (Polypropylene, manufactured by Prime Polymer Co., Ltd., F-704NP) Adhesive layer (γ): γ-1 (modified polypropylene QF-500, manufactured by Mitsui Chemicals, Inc.) Sealant layer (α): The resin composition obtained in Reference Example 5 above Apparatus: 5-type 5-layer inflation extrusion molding machine (manufactured by Dr Collin) Die temperature: 210°C Blow-up ratio: 2.7 Take-up speed: 4 m / min Folded film width: 25 cm (Conditions for thermoplastic resin layer (δ) extruder 1) Extruder: 30φ single-screw extruder (manufactured by Dr Collin) Rotational speed: 60 rpm Extrusion temperature: Feed zone / Compression zone / Metering zone = 170°C / 190°C / 210°C (Conditions for thermoplastic resin layer (δ) extruder 2) Extruder: 20φ single-screw extruder (manufactured by Dr Collin) Rotational speed: 70 rpm Extrusion temperature: Feed zone / Compression zone / Metering zone = 170°C / 190°C / 210°C (Conditions for thermoplastic resin layer (δ) extruder 3) Extruder: 20φ single-screw extruder (manufactured by Dr Collin) Rotational speed: 70 rpm Extrusion temperature: Feed zone / Compression zone / Metering zone = 170°C / 190°C / 210°C (Conditions for adhesive layer (γ) extruder) Extruder: 20φ single-screw extruder (manufactured by Dr Collin) Rotational speed: 70 rpm Extrusion temperature: Feed zone / Compression zone / Metering zone = 170°C / 190°C / 210°C (Conditions for sealant layer (α) extruder) Extruder: 30φ single-screw extruder (manufactured by Dr Collin) Rotational speed: 24 rpm Extrusion temperature: Feed zone / Compression zone / Metering zone = 190°C / 210°C / 210°C The obtained multilayer film was measured for OTR and the width-direction uniformity of OTR according to the methods described in Evaluation Methods (11) and (12) above. The results are shown in Table 14.
[0188] A 12 μm thick PET film (PET12) was laminated onto the obtained multilayer film via an adhesive layer (γ) as a base layer (β), creating a multilayer structure with a layer configuration of base layer (β) / adhesive layer (γ) / thermoplastic resin layer (δ) / adhesive layer (γ) / sealant layer (α). When laminating the base layer (β), a two-component urethane adhesive ("Takelac A-520" and "Takenate A-50" manufactured by Mitsui Chemicals, Inc.) was applied to create an adhesive layer (γ') with a dry thickness of 2 μm, and the multilayer structure was obtained by lamination using the dry lamination method. The heat seal strength and appearance of the obtained multilayer structure were evaluated using the method described in evaluation method (13) above, and the results are shown in Table 12. The other evaluation results for the dried resin composition pellets used in Reference Example 5 are reproduced in Tables 13 and 14.
[0189] <Example 11> In a 60L stirring tank equipped with a jacket, stirrer, and reflux condenser, 1.6 kg of the crudely dried EVOH(A1) obtained in Synthesis Example 1, 0.4 kg of the crudely dried EVOH(A7) obtained in Synthesis Example 7, 0.8 kg of water, and 2.2 kg of MeOH were charged and stirred at 60°C for 5 hours to completely dissolve. Sorbic acid, crotonaldehyde, 2,4-hexadienal, and 2,4,6-octatrienal were added to the resulting solution. This solution was extruded through a 4 mm diameter gold plate into a water / MeOH = 90 / 10 mixture cooled to -5°C to precipitate in strand form, and these strands were cut into pellets with a strand cutter to obtain hydrated EVOH pellets. The moisture content of the obtained hydrated EVOH pellets was measured using a Mettler halogen moisture meter "HR73" and was found to be 52% by mass.
[0190] The obtained hydrated EVOH pellets were placed in a 1 g / L aqueous acetic acid solution (bath ratio 20) and stirred and washed for 2 hours. After desaturation, the pellets were placed again in a 1 g / L aqueous acetic acid solution (bath ratio 20) and stirred and washed for 2 hours. After desaturation, the aqueous acetic acid solution was replaced and the same procedure was repeated. The pellets washed in aqueous acetic acid solution and then desaturated were placed in deionized water (bath ratio 20) and stirred and washed for 2 hours, and desaturated. This process was repeated three times until the electrical conductivity of the washing solution was 3 μS / cm or less (measured with Toa Denpa Kogyo Co., Ltd.'s "CM-30ET"), thereby obtaining hydrated EVOH pellets from which the catalyst residue from the saponification reaction had been removed.
[0191] The obtained water-containing pellets were placed in an aqueous solution (bath ratio 20) with a sodium acetate concentration of 0.510 g / L, an acetic acid concentration of 0.8 g / L, a phosphoric acid concentration of 0.04 g / L, and a boric acid concentration of 0.05 g / L, and chemically treated by immersion for 4 hours with periodic stirring. These pellets were dehydrated and dried at 80°C for 3 hours and at 105°C for 16 hours under a nitrogen stream with an oxygen concentration of 1 volume% or less to obtain cylindrical (average diameter 2.8 mm, average height 3.2 mm) dried resin composition pellets containing EVOH (A1 and A7), acetic acid, phosphoric acid, sodium ions (sodium salt), crotonaldehyde, 2,4-hexadienal, 2,4,6-octatrienal, and sorbic acid. The obtained dried resin composition pellets were evaluated according to the methods described in evaluation methods (2), (3), (5) to (9) above. The sodium ion content in the dried resin composition pellets was 100 ppm, the phosphoric acid content was 40 ppm (based on phosphate root equivalent), and the acetic acid content was 200 ppm. The content of each component other than EVOH is based on the EVOH content. Other evaluation results are shown in Tables 13 and 14. The amounts of each component added were adjusted so that the content of crotonaldehyde, 2,4-hexadienal, 2,4,6-octatrienal, and sorbic acid were as shown in Table 13.
[0192] Multilayer films and multilayer structures were prepared and evaluated in the same manner as in Example 10, except that the dried resin composition pellets obtained above were used. The results are shown in Table 14.
[0193] <Examples 13, 15, 16, Comparative Examples 3, 4> As shown in Table 13, dry resin composition pellets, multilayer films, and multilayer structures were prepared and evaluated in the same manner as in Example 11, except that the type of EVOH(Aa), the type of EVOH(Ab), the mass ratio (Aa) / (Ab), the boric acid content, the unsaturated aldehyde (B) content, and the conjugated polyene (C) content were changed. The sodium ion content in the dry resin composition pellets was 100 ppm, the phosphoric acid content was 40 ppm (calculated as phosphate root), and the acetic acid content was 200 ppm. The content of each component other than EVOH is based on the EVOH content. Other evaluation results are shown in Tables 13 and 14. The boric acid concentration of the aqueous solution used in the chemical treatment was adjusted as appropriate so that the boric acid content of the resulting dry resin composition pellets was as shown in Table 13.
[0194] <Example 12> 80 parts by mass of dry resin composition pellets obtained in Reference Example 5 and 20 parts by mass of dry resin composition pellets obtained in Reference Example 3 were dry blended to obtain a group of dry resin composition pellets. The obtained group of dry resin composition pellets was extruded using a 30 mmφ twin-screw extruder (TEX-30SS-30CRW-2V, manufactured by Japan Steel Works Ltd.) under the conditions of an extrusion temperature of 200°C, a screw rotation speed of 300 rpm, and an extrusion resin rate of 25 kg / hour. After pelletizing, the pellets were hot-air dried at 80°C for 2 hours to obtain dry resin composition pellets. The obtained dry resin composition pellets were evaluated according to the methods described in evaluation methods (2), (3), (5) to (9), (11), and (12) above. The results are shown in Tables 13 and 14. Multilayer films and multilayer structures were prepared in the same manner as in Example 10, except that the dry resin composition pellets obtained above were used, and the evaluations described in (13) to (15) above were performed. The evaluation results are shown in Table 14.
[0195] <Example 14> Dry resin composition pellets were obtained in the same manner as in Example 11, except that 90 parts by mass of dry resin composition pellets obtained in Reference Example 48 and 10 parts by mass of EVOH(A9) pellets obtained in Synthesis Example 9 were dry-blended. The obtained dry resin composition pellets were evaluated according to the methods described in evaluation methods (2), (3), (5) to (9), (11), and (12) above. The results are shown in Tables 13 and 14. A multilayer structure was prepared in the same manner as in Example 10, except that the dry resin composition pellets obtained above were used, and the evaluations described in (13) to (15) above were performed. The evaluation results are shown in Table 14.
[0196] [Table 13]
[0197] [Table 14]
[0198] As shown in Tables 11-14, the multilayer structures prepared in Examples 1-15 exhibited good heat seal strength and appearance, while the multilayer structures prepared in Comparative Examples 1-4 received poor evaluations for heat seal strength and appearance. The resin compositions used as raw materials for the heat seal layer (α) in the examples all showed good evaluation results for die build-up and neck-in resistance, and it is presumed that these evaluation results influenced the heat seal strength and appearance. Furthermore, from the results of each reference example, it can be seen that in the resin composition used for the sealant layer (α), good neck-in resistance is achieved when b1 / (b2+b3) is 2.0 or more and less than 150.0, and die build-up is suppressed when b2+2b3 is 0.65 ppm or less. From this, it can be seen that by using a resin composition in the sealant layer (α) where b1 / (b2+b3) is 2.0 or more and less than 150.0, and b2+2b3 is 0.65 ppm or less, a multilayer structure with good heat seal strength and appearance can be obtained.
[0199] With respect to the single-layer films obtained in Examples 1 to 9, the adsorption amount of synthetic pyrethroid and the adsorption amount of nicotine were evaluated by the following evaluation methods. (Evaluation Methods) After weighing 40 mg of synthetic pyrethroid or nicotine, a weighing bottle with an internal volume of 50 cm 3 was charged with the substance, and a SUS mesh processed into a U-shape was placed therein so as not to come into contact with the adsorbed substance. One piece of film cut out from the single-layer film and having a width of 1 cm and a length of 4 cm was placed on the mesh plate, and the whole was allowed to stand for 2 weeks in an environment of 20°C and 50% RH. A film piece of a size more suitable for the adsorption amount was used, and the adsorption amount was measured by the method described below. (Measurement of Adsorption Amount) For the measurement of the adsorption amount, a thermal desorption gas chromatograph-mass spectrometer (TCT-GC / MS, TCT: "CP-4020" manufactured by Chrompack, GC / MS: "Model 5973" manufactured by Agilent) was used, and the adsorption amount was measured by the following method. (Gas Collection Method) The film piece was placed in a glass chamber heated to 80°C. While flowing clean nitrogen from one side at a flow rate of 100 ml / min, a Tenax collection tube was attached to the other side, and the gas distilled out for 3 minutes was collected to serve as a sample. (Gas Desorption Conditions) The Tenax collection tube was heated to 250°C for desorption. (GC Introduction Method) After the desorbed gas was cold-trapped at -130°C, it was heated to 250°C and introduced into the gas chromatograph to measure the adsorption amount. (Evaluation Criteria) Synthetic pyrethroid adsorption amount A: 1 ng / cm 2 less than B: 1 ng / cm 2 or more and less than 10 ng / cm 2 less than C: 10 ng / cm 2 or more Nicotine adsorption amount A: 500 ng / cm 2 less than B: 500 ng / cm 2 or more and less than 1000 ng / cm 2 less than C: 1000 ng / cm 2 That's all.
[0200] <Comparative Example 5> The amount of synthetic pyrethroid and nicotine adsorbed was evaluated using the above evaluation method for the LLDPE film "TUX(trademark) MC-S" (thickness 30 μm) manufactured by Mitsui Chemicals Tohcello, Inc.
[0201] The adsorption amounts of synthetic pyrethroid and nicotine of the single-layer films obtained in Examples 1 to 9 were all rated "A," whereas the adsorption amounts of synthetic pyrethroid and nicotine of the LLDPE film used in Comparative Example 5 were all rated "C." This evaluation result demonstrates the usefulness of the non-adsorption properties of the heat-seal layer (α) for the compounds it covers.
Claims
1. The material comprises a sealant layer (α) made of a resin composition and a base layer (β) containing a thermoplastic resin with a melting point of 190°C or higher, with the sealant layer (α) on the outermost surface. The above resin composition comprises an ethylene-vinyl alcohol copolymer (A) having an ethylene unit content of 20 mol% or more and 60 mol% or less, and crotonaldehyde (B1), and further comprises at least one selected from the group consisting of 2,4-hexadienal (B2) and 2,4,6-octatrienal (B3), The above resin composition is a multilayer structure that satisfies the following formulas (1) and (2). 2.0≦b 1 / (b 2 +b 3 )<150.0 ・・・(1) b 2 +2b 3 ≦0.65 ・・・(2) In the above formulas (1) and (2), b 1 This is the content (ppm) of crotonaldehyde (B1) in ethylene-vinyl alcohol copolymer (A), and b 2 This is the content (ppm) of 2,4-hexadienal (B2) in ethylene-vinyl alcohol copolymer (A), and b 3 This is the content (ppm) of 2,4,6-octatrienal (B3) relative to the ethylene-vinyl alcohol copolymer (A).
2. In the above resin composition, the total content of crotonaldehyde (B1), 2,4-hexadienal (B2) and 2,4,6-octatrienal (B3) relative to the ethylene-vinyl alcohol copolymer (A) (b 1 + b 2 + b 3 ) is 0.01 ppm or more and 7.0 ppm or less, the multilayer structure according to claim 1.
3. In the above resin composition, the content of crotonaldehyde (B1) is b 1 The multilayer structure according to claim 1 or 2, wherein the concentration is 0.01 ppm or more and 4.0 ppm or less.
4. In the above resin composition, the content of 2,4-hexadienal (B2) is b 2 The multilayer structure according to claim 1 or 2, wherein the concentration is 0.005 ppm or more and 0.65 ppm or less.
5. In the above resin composition, the content of 2,4,6-octatrienal (B3) is b 3 The multilayer structure according to claim 1 or 2, wherein the concentration is 0.325 ppm or less.
6. The multilayer structure according to claim 1 or 2, wherein the resin composition further comprises a conjugated polyene compound (C), and in the resin composition, the content c of the conjugated polyene compound (C) relative to the ethylene-vinyl alcohol copolymer (A) is 1 ppm or more and less than 300 ppm.
7. The multilayer structure according to claim 6, wherein the conjugated polyene compound (C) is sorbic acid.
8. The multilayer structure according to claim 1 or 2, wherein a sealant layer (α) and a substrate layer (β) are laminated via an adhesive layer (γ).
9. The multilayer structure according to claim 1 or 2, having a multilayer film in which a sealant layer (α), an adhesive layer (γ), and a substrate layer (β) are directly laminated in this order.
10. The ethylene-vinyl alcohol copolymer (A) comprises ethylene-vinyl alcohol copolymer (Aa) and ethylene-vinyl alcohol copolymer (Ab), The difference in melting points (Aa-Ab) between the ethylene-vinyl alcohol copolymer (Aa) and the ethylene-vinyl alcohol copolymer (Ab) is 8°C or more. The multilayer structure according to claim 1 or 2, wherein the mass ratio (Aa / Ab) of ethylene-vinyl alcohol copolymer (Aa) to ethylene-vinyl alcohol copolymer (Ab) is 60 / 40 or more and 95 / 5 or less.
11. The multilayer structure according to claim 1 or 2, wherein at least a portion of the ethylene-vinyl alcohol copolymer (A) contains at least one structural unit selected from the group consisting of structural units represented by the following formula (I) and structural units represented by the following formula (II) in an amount of 0.3 mol% to 40 mol% relative to the total vinyl alcohol units of the at least portion of the ethylene-vinyl alcohol copolymer (A). 【Chemistry 1】 [In the above formula (I), R 1 , R 2 and R 3 Each of these independently represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 10 carbon atoms, an alicyclic hydrocarbon group having 3 to 10 carbon atoms, an aromatic hydrocarbon group having 6 to 10 carbon atoms, or a hydroxyl group. 1 , R 2 and R 3 One pair of them may be joined (however, R 1 , R 2 and R 3 (Except when one of the pairs consists of hydrogen atoms.) Some or all of the hydrogen atoms in the above-mentioned aliphatic hydrocarbon group having 1 to 10 carbon atoms, alicyclic hydrocarbon group having 3 to 10 carbon atoms, and aromatic hydrocarbon group having 6 to 10 carbon atoms may be substituted with hydroxyl groups, alkoxy groups, carboxyl groups, or halogen atoms. In the above formula (II), R 4 , R 5 , R 6 and R 7 Each of these independently represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 10 carbon atoms, an alicyclic hydrocarbon group having 3 to 10 carbon atoms, an aromatic hydrocarbon group having 6 to 10 carbon atoms, or a hydroxyl group. 4 and R 5 That is, or R 6 and R 7 This means that they may be joined (however, R 4 and R 5 toga, or R 6 and R 7 (However, this excludes the case where both are hydrogen atoms.) Some or all of the hydrogen atoms in the above-mentioned aliphatic hydrocarbon groups having 1 to 10 carbon atoms, alicyclic hydrocarbon groups having 3 to 10 carbon atoms, and aromatic hydrocarbon groups having 6 to 10 carbon atoms may be substituted with hydroxyl groups, alkoxy groups, carboxyl groups, or halogen atoms.
12. The multilayer structure according to claim 1 or 2, further comprising a layer (δ) containing a thermoplastic resin having a melting point of less than 190°C.
13. A multilayer structure according to claim 1 or 2, wherein the heat seal strength measured at a tensile speed of 300 mm / min in accordance with JIS Z1707 (2019) is 20 N / 15 mm or more when the sealant layers (α) of the multilayer structure are pressed together for 1 second using a hot plate type heat sealer at a temperature of 200°C and a pressure of 0.1 MPa.
14. A packaging bag comprising the multilayer structure described in claim 1 or 2.
15. A vacuum insulator comprising the multilayer structure described in claim 1 or 2.
16. The adsorption amount of synthetic pyrethroid in the sealant layer (α) is 10 ng / cm³. 2 A multilayer structure according to claim 1 or 2, wherein the multilayer structure is less than [amount missing].
17. Nicotine adsorption amount of sealant layer (α) is 1000 ng / cm² 2 A multilayer structure according to claim 1 or 2, wherein the multilayer structure is less than [amount missing].
Citation Information
Patent Citations
Insect-proofing material
JP2004254599A
Heat seal film and wrapper bag
JP2012041076A
Single-layer film, vapor-deposition film, multilayer film and heat seal film
JP2022032037A
Vapor-deposited film, packaging material and vacuum insulation
JP2023084665A
Resin composition containing ethylene-vinyl alcohol copolymer
WO2013146961A1